Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 1844133632 species occurrences available in GBIF matching the query: (Query is too complex. Can be viewed on the landing page) The dataset includes 1844133632 records from 32646 constituent datasets: 39 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 25 records from Schulteich Heinrich-Mann-Schule. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 115 records from Revision of the Central American and Mexican species of the Curtonotum murinum species complex (Diptera: Curtonotidae). 379 records from Implementación de la bioindicación en el Río Magdalena - 2015. 2854 records from marine sediment metagenome Metagenome. 3297 records from Dados da ocorrência de plantas lenhosas em uma cronossequência em área de Caatinga, Parque Nacional do Catimbau, Buíque, PE, Brasil. 4 records from Range table from benthic foraminifers in ODP Hole 146-889A. 71 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 1696 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 363 records from Bannwald Burghauser Forst. 948 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 296055 records from R. L. McGregor Herbarium Vascular Plants Collection. 13 records from Coccolith counts of multinet M32/5_MSN988. 6 records from A review of the subfamily Anobinae with the description of a new species of Baniana Walker from North and Central America (Lepidoptera, Erebidae, Anobinae). 198 records from Phytoplankton abundance in surface water during Professor Vodyanitskiy cruise PV30_1. 290 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 5 records from Oosagitta gen. nov. from tropical Africa, with revision of two species and description of four new species (Coleoptera: Chrysomelidae, Galerucinae). 59390 records from LiquenCAT: Banco de datos de los líquenes de Cataluña. 156 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 5 records from Marmacuma samimei gen. et sp. nov., (Peracarida; Cumacea; Nannastacidae) from Tarantian (Upper Pleistocene) sediments from the Sea of Marmara, Turkey. 9 records from Three new species of Lecteria Osten Sacken, 1888 (Diptera: Tipulidae) from a scientific survey in Mitaraka (French Guiana). 4 records from The first record of genus Gryllomorpha Fieber in Romania (Orthoptera: Gryllidae: Gryllomorphinae). 27 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 342 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 10114 records from 臺灣特有生物研究保育中心植物標本館(TAIE)苔蘚資料. 2315 records from Monitoreo de la abundancia, riqueza y biodiversidad de aves del Santuario de Flora y Fauna Galeras de 2009 a 2014. 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 2871 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 11 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 466 records from CBS Bacteria Database. 126 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/092-3. 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 20 records from Notes on the Stenus indubius group with descriptions of four new species from China (Coleoptera, Staphylinidae). 9391 records from Bryophyte specimens of The Nagoya University Museum. 1860 records from Estudio poblacional del chano norteño, Micropogonias megalops y la curvina Golfina Cynoscion othonopterus (Gilbert) (Pisces: Sciaenidae), especies endémicas del Alto Golfo de California, México. 12 records from The fossil record of the family Benthopectinidae (Echinodermata, Asteroidea), a reappraisal. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 32063 records from University of Guam Insect Collection. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 1 records from A new species of the mesopelagic isopod genus Xenuraega Tattersall, 1909 (Crustacea: Isopoda: Aegidae) from Japan, the second species in the genus. 4 records from Morphology of pupae of the Pyropteron (Synansphecia) triannuliforme-group (Lepidoptera: Sesiidae). 151 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 5418 records from Données des membres de l'Association française d'Arachnologie. 172 records from Artenvielfalt des "Grünen Klassenzimmers". 9 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 69 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Vireonidae. 2814 records from Chronicle of Nature - Phenology of Birds of Pinezhsky State Nature Reserve. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 32 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 85 records from Revision of world species of the genus Oreiscelio Kieffer (Hymenoptera, Platygastroidea, Platygastridae). 36 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 83 records from Nannofossil abundance of Hole 24-232. 1 records from Ueber eine noch nicht beschriebene Nothrus-Art. 31 records from The Plecoptera of Panama. II. Two new species, one new country record, and additional locality records of Anacroneuria (Perlidae) from western Panama. 165 records from AMAPPS Southeast Aerial Cruise Fall 2016. 4 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 2 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 5 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1 records from A new aberrant Doryctinae genus (Hymenoptera: Braconidae) from French Guiana. 1189 records from UWIZM Molluscs. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 14 records from An annotated checklist of Ciidae (Coleoptera: Tenebrionoidea) of Iran. 6 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 5413 records from MCP-Aves - Coleção de Aves. 70 records from Área Selva de Florencia- Cantidad de área ocupada selva_2018. 3 records from Hidden diversity in European bees: Andrenaamieti sp. n., a new Alpine bee species related to Andrenabicolor (Fabricius, 1775) (Hymenoptera, Apoidea, Andrenidae). 135 records from Nannofossil abundance of Hole 36-329. 51 records from Revision of the French Polycirridae (Annelida, Terebelliformia), with descriptions of eight new species. 4 records from Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae). 29 records from The genus Chalybion Dahlbom, 1843 (Hymenoptera: Sphecidae) from Northwest Vietnam, with description of a new species. 100 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 76704 records from EDP Foz Tua: Terrestrial Birds, Spring (point counts) - Ecological Monitoring Program [2011-2017]. 824 records from Bird specimens of Saitama Museum of Natural History. 310 records from orthopteracollections-nhmj-ioj. 2 records from Carnivores of Syria. 1054 records from Vertebrados terrestres de San Juan de Camarones, Durango. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 5409 records from The Indigo Project: a global citizen science Ocean survey. 304 records from Diagnostic des Espaces Naturels Sensibles des Yvelines. 3 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 7 records from Redescription of the types of species of Anastatus Motschulsky, 1859 (Hymenoptera: Chalcidoidea: Eupelmidae) described by J. K. Sheng and coauthors. 10883 records from Collections of Bioclass, school #179, Moscow. 579 records from Données du/de la naturaliste Houpert Sylvain provenant de la base de donnée du SINP Île-de-France CETTIA. 870693683 records from EOD – eBird Observation Dataset. 1 records from Arcanumophis, a new genus and generic allocation for Erythrolamprus problematicus (Myers 1986), Xenodontinae (Colubridae) from the Cordillera de Carabaya, southern Peru. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 52874 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2016. 20 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 4 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 14 records from New seriated Amathia species in Japan, with a redescription of A. acervata Lamouroux, 1824 (Bryozoa: Ctenostomata). 7 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 988 records from flower availability 2008 Alb-korrigiert. 14558 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 206 records from Gross body measurements of Antarctic Rock Cod (Trematomus bernacchii) collected at sites adjacent to Casey Station 2012/13. 282 records from Middlebury College Bee Collection. 43 records from The megisthanid mites (Mesostigmata: Megisthanidae) of Australia. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 42 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 301296 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 8800 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 7 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 41308 records from TPWD HARC Texas Coastal Fisheries San Antonio Bay Trawl. 3 records from New species of Alpinalona Alonso & Sinev, 2017 (Cladocera: Anomopoda: Chydoridae) from South-East USA. 218 records from West African pholcid spiders: an overview, with descriptions of five new species (Araneae, Pholcidae). 2793 records from Pat Livermore's Fungus Records 1976 - 2000. 11 records from The genus Cylloepus Erichson, 1847 (Coleoptera: Elmidae: Elminae) new species and combinations. 11 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 10 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from Benthic macrofauna abundance of sediment core 12930-063. 34 records from The Moroccan species of Chyromyidae (Diptera) with descriptions of five new species of Aphaniosoma Becker. 73781 records from IAN herbarium - Embrapa Amazônia Oriental - Herbário Virtual REFLORA. 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 6 records from Collection Amphibia fossil SMF. 2865 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleobotany National Collection (BAPb). 22 records from A description of the flea species Paractenopsyllus madagascarensis n. sp. and the female sex of Paractenopsyllus raxworthyi Duchemin & Ratovonjato, 2004 (Siphonaptera, Leptopsyllidae) from Madagascar with a key to the species of Paractenopsyllus. 67 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 8810 records from Données naturalistes de Benoit MARTHA. 114 records from Especies de peces registradas en el canal principal y afluentes de los ríos Lengupá y Upía en Boyacá. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 120512 records from Observations occasionnelles Parc national des Pyrénées. 6 records from A contribution to the knowledge of Dermestidae (Coleoptera) from Guatemala. 4 records from A new species of Decimiana Uvarov from Brazil, with updated key to species and remarks on their geographic distribution (Mantodea: Acanthopidae, Acanthopinae). 120 records from BIRDRACE The early birds. 3 records from Two new Brazilian species of Neapion Alonso-Zarazaga, 1990 subgenus Neotropion Alonso-Zarazaga, 1990 with a key to South American species (Brentidae: Apioninae). 5 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 17 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mercedes (Unterkofler, octubre 1999). 1 records from A new species of the genus Protoplotina Miyatake (Coleoptera: Coccinellidae) from India. 96 records from Overview of the Anyphaenids (Araneae, Anyphaeninae, Anyphaenidae) spider fauna from the Chocó forest of Ecuador, with the description of thirteen new species. 24645 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 11 records from Gulf of Maine Razorbill Tracking (aggregated per 1-degree cell). 1 records from A new species of Centrouropoda (Acari: Uropodidae: Uropodina), with a key to the world species of the genus. 6101 records from MfN - Mallophaga Collection. 167 records from An overlooked diversity-the Costellariidae (Gastropoda: Neogastropoda) of the Miocene Paratethys Sea. 2 records from Synchrotron micro-CT scanning leads to the discovery of a new genus of morphologically conserved echinoid (Echinodermata: Cassiduloida). 3 records from Nannofossil abundance of Hole 6-53A. 10 records from Nannofossil abundance of Hole 29-283A. 105 records from MIRC NAVFAC Incidental Sightings - Aerial 1965-2014. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 13 records from Potamotrygon boesemani (Chondrichthyes: Myliobatiformes: Potamotrygonidae), a new species of Neotropical freshwater stingray from Surinam. 5262 records from Spider Mites Collection of Jean Gutierrez. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 1 records from A new name for Dendronephthya kukenthali Gravier, 1908 (Octocorallia, Nephtheidae): Dendronephthya perezi nom. n.. 15 records from The genus Calodera Mannerheim in Canada (Insecta, Coleoptera, Staphylinidae, Aleocharinae). 2132 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 3 records from Molecular phylogenetics, PCA, and MFA recover a new species of Cyrtodactylus (Squamata: Gekkonidae) from an isolated sandstone massif in northwestern Cambodia. 49328 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 4 records from hips of Epidrepanus within the subtribe Drepanocerina (Coleoptera: Scarabaeidae: Scarabaeinae: Oniticellini), with the description of two new species. 318 records from Orthoptera Tettigoniidae as indicators of biodiversity hotspots in the Guinean Forests of Central and West Tropical Africa. 3 records from Cosmocerca acanthurum n. sp. (Nematoda: Cosmocercidae) in Pseudoeurycea leprosa and Chiropterotriton orculus from the Transmexican Volcanic Belt, Central Mexico, with a checklist of the helminth parasites of plethodontid salamanders. 1142 records from Records of the Victorian Conservation Seedbank. 3 records from Microlaimus capitatus sp. n. and Dichromadora simplex Timm, 1961 (Nematoda, Chromadorea) from the coast of Vietnam. 54 records from Revision of the genus Lamprima Latreille, 1804 (Coleoptera: Lucanidae). 193 records from Relative abundances of Florisphaera profunda and Helicosphaera carteri during the sapropel S5 of sediment core MD81-LC21. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 24 records from The geometrid moths of Ethiopia I: tribes Pseudoterpnini and Comibaenini (Lepidoptera: Geometridae, Geometrinae). 14 records from First study of the Polycladida (Rhabditophora, Platyhelminthes) from the Pacific Coast of Costa Rica. 112 records from Antarctic Pycnogonids II. 58881 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 87 records from Microfossil abundance of Hole 18-173. 546 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 19 records from Review of the dwarf Glossogobius lacking head pores from the Malili lakes, Sulawesi, with a discussion of the definition of the genus.. 335 records from (Table 3) Distribution of calcareous nannofossils at DSDP Site 82-563 in the North Atlantic. 6979 records from Upper Silesian Museum, Bird Observations. 149 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 14110 records from Other Mammal Data from National Dormouse Monitoring Programme (NDMP). 5 records from Morphological and molecular description of a new genus and species of black coral (Cnidaria: Anthozoa: Hexacorallia: Antipatharia: Antipathidae: Blastopathes) from Papua New Guinea. 126 records from SEWBReC Springtails and allies (South East Wales). 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 860613 records from Collation of spatial seagrass data from 1984 - 2014 for the Great Barrier Reef World Heritage Area (GBRWHA) (NESP TWQ 3.1, TropWATER, JCU), Australia (1984-2014). 28742 records from Pacific Reef Assessment and Monitoring Program: Rapid Ecological Assessments of Fish Large-Area Stationary Point Count Surveys (SPC) at Coral Reef Sites across the Pacific Ocean from 2000 to 2007. 62 records from Polychaeta and Oligochaeta of the Auckland and Campbell Islands, New Zealand, 1941-1945. 749 records from Carabidae of Wales and England. 2 records from Orientatractis brycini sp. nov. (Nematoda: Atractidae) from characiform freshwater fishes in Gabon, Africa. 163716 records from The Himalayan Uplands Plant database (HUP Version 1). 127 records from Artenvielfalt auf dem Schulgelände. 2 records from A new species of Leandra (Melastomataceae, Miconieae) from Atlantic Forest, Southeastern Brazil. 5 records from Two new littoral species of the genus Anurida Laboulbène, 1865 (Collembola, Neanuridae) from the Pacific coast of Asia. 8425 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 36 records from Triticale French National Collection. 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 16 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 7894 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 4 records from Miliusa gokhalaei, a new species of Annonaceae from India with notes on interrelationships, population structure and conservation status. 69 records from BIRDRACE Pfeifenten. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 2275 records from Marine metagenome ICM_JRV. 187 records from Données de la structure ONEMA/AFB provenant de la base de donnée du SINP Île-de-France CETTIA. 147 records from Données de la naturaliste Laurence Beauchamp. 123 records from Ladybirds of Ireland. 321 records from Collections ichtyologiques et herpétologiques (BOUM). 23 records from The world species of Ophthalmothrips Hood (Thysanoptera; Phlaeothripidae), with new records from Africa, China and Japan. 7 records from A new species of the genus Takydromus (Squamata, Lacertidae) from southwestern Guangdong, China. 78 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 55 records from Temporary expansion to shelf depths rather than an onshore-offshore trend: the shallow-water rise and demise of the modern deep-sea brittle star family Ophiacanthidae (Echinodermata: Ophiuroidea). 1 records from The giant “ penis ” of a newly described species in the subgenus Scotoconiopteryx from Peru (Neuroptera: Coniopterygidae: Coniopteryginae: Coniopteryx). 16 records from Données naturalistes de ROLLAND Blandine. 26 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 570 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 2 records from Description of the female of Dicterias atrosanguinea Selys 1853, with notes on male genital ligula and male behavior (Odonata: Dicteriadidae). 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 49 records from La Paya, censo rápido de la flora de Jirijiri. 88 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 32 records from Morphological differences between Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) (Crustacea, Decapoda, Brachyura, Majoidea). 6192 records from NE Scotland fish records 1800-2010. 3 records from Distribution Of Moselia Infuscata (Claassen, 1923) (Plecoptera: Leuctridae) In Canada. 25 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 74 records from Taxonomy and Biogeography without frontiers – WhatsApp, Facebook and smartphone digital photography let citizen scientists in more remote localities step out of the dark. 3 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 25 records from Cochlostoma revised: the subgenus Lovcenia Zallot et al., 2015 (Caenogastropoda, Cochlostomatidae). 223715 records from Ocean Salmon Program - Barkley Sound Juvenile Salmon Study from 1987 to 1994. 11 records from On the Bennelongia nimala and B. triangulata lineages (Crustacea, Ostracoda) in Western Australia, with the description of six new species. 6 records from Coccoliths in sediment core PS1532-9. 71 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 175 records from NMML Killer Whale Vessel, Bering Sea, 1992. 41 records from MIRC KB23 Shoreline Surveys May 2013. 252 records from bmhs_weatherheadshell_collection. 57898 records from Fichier communal des ongulés. 103 records from Morphological and anatomical investigation of New Caledonian graminoid Dendrobium (Orchidaceae) with the description of two new species. 4298 records from ColRest_Raw1. 34 records from Chronicle of Nature - Phenology of Arachnids of FSBI Zeya State Nature Reserve. 19 records from A new species of Panaqolus (Siluriformes: Loricariidae) from the rio Madeira basin with remarkable intraspecific color variation. 11 records from Nannofossil abundance of Hole 4-25. 3 records from A new species of Eupatorus Burmeister, 1847 related to Eupatorus birmanicus Arrow, 1908 from southwestern China (Coleoptera: Scarabaeidae: Dynastinae). 57 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 5678 records from SNH Bat Casework records 1970-2007. 17 records from Universidad de San Carlos de Guatemala - Colección de Equinodermos. 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 11 records from Description of the first Caribbean Oscarellidae (Porifera: Homoscleromorpha). 7 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 9176 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 1708 records from Chronicle of Nature - Phenology of Plants of Kaniv Nature Reserve. 205 records from Living Cirripedia. 2 records from A contribution to the knowledge of the genera Fissocantharis Pic, 1921 and Micropodabrus Pic, 1920 from Taiwan (Coleoptera, Cantharidae). 4 records from Studies in Mexican Grasshoppers: Liladownsia fraile, a new genus and species of Dactylotini (Acrididae: Melanoplinae) and an updated molecular phylogeny of Melanoplinae. 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 1283 records from Données du/de la naturaliste Barande Serge provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 154239 records from flora&fauna(NIBR)2019. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 219 records from Land and freshwater molluscs of Northern Spain. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3775 records from Données naturalistes de Charlotte PICARD. 4 records from Ostracoda abundance of Hole 44-390. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 131 records from Manejo campesino sustentable del maguey papalote del Chilapan. Fase II. 13003 records from University of Nebraska State Museum Birds Collection. 1777 records from Herbarium BSG Lichenes. 813 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE233. 18 records from Cast netting new species: Integrative taxonomy of Distichodus notospilus (Characiformes: Distichodontidae) discovers new species and overlooked areas of endemism in Central Africa. 679 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 19 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 88 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 1287 records from Birds - Wild Birds (KIDR-BI). 251 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 139 records from Revision of the subgenus Stigmatophorella of Chalcophorella (Coleoptera: Buprestidae: Chrysochroinae). 55 records from The Genus Daspletis Loew, 1858 And The Description Of Two New Genera, Anasillomos And Remotomyia (Diptera: Asilidae: Stenopogoninae). 4 records from A new rotifer species: Lecane langsenensis n. sp. (Rotifera: Monogononta) from Vietnam. 71 records from (Figure 9) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644A cores 7-12. 18 records from Naturtag. 20583 records from Herbier Louis-Marie (QFA) - Collection de lichens. 73 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 115 records from Swedish Malaise Trap Project (SMTP) - Vespinae. 29 records from Review of Glaphyrosoma (Orthoptera: Stenopelmatoidea: Anostostomatidae) including new species and biological information. 40 records from HRC CRC Small Vessel-Based Monitoring Surveys July 2006. 926 records from suspended particulate matter Raw sequence reads. 8 records from Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae). 193 records from A Compendium Of Distributional Records For Oroperla Barbara Needham, 1933 (Plecoptera: Perlodidae), With Additional Documentation Of Reproductive Morphology And Biology. 4 records from Taxonomic revision of the Neotropical genus Ectophasiopsis Townsend, 1915 (Diptera: Tachinidae: Phasiinae). 47 records from The Philippine hair wax spiders and their relatives: revision of the Pholcus bicornutus species group (Araneae, Pholcidae). 595200 records from Plant. 44 records from Megafauna abundance and biomass in surface sediment during cruise PLG95A. 31 records from Taxonomic review and distribution of the genus Vespula Thomson, 1869 (Hymenoptera: Vespidae: Vespinae) from Vietnam. 26 records from (Table 1) Chemical composition of segregations and groundmass seperates of ODP Leg 135 samples. 21 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 123 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 124 records from Pollen profile 2 from Richland Creek. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 363 records from Données du/de la naturaliste Kohn Annie provenant de la base de donnée du SINP Île-de-France CETTIA. 1912 records from Données naturalistes de la Société pour le Muséum d'Orléans et les Sciences (SOMOS). 78458 records from Inventaire de la flore de Dordogne 2017. 4318 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 24 records from Chapter 7: Linnaean Plant Names and their Types (part Q). 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 15 records from Contributions to the knowledge of Dichelops (Dichelops) with the description of a new species (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 24 records from Steinbruch Mainz-Weisenau, 4.Jahr. 12859 records from Colecção Entomológica IIA. 56 records from Colección de Zoología Universidad Icesi: Insectos. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 17034 records from MZFC/Coleccion de Aves. 1190 records from Coleópteros presentes en un proceso de restauración pasiva en bosque seco tropical. 113500 records from TNHC Herpetology Collection. 354 records from Avifauna asociada a los manglares de Tribugá - Nuquí, 2016. 1059783 records from Tasmanian Natural Values Atlas. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 9 records from ZUEC-POR - Coleção de Porifera do Museu de Zoologia da UNICAMP. 625 records from Inventario de la biota terrestre (florístico) y marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel (Plantas). 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 3764 records from Swiss National Cicadidae Databank. 2 records from Two new species of Acontias (Acontinae, Scincidae) from the Mpumalanga Highveld escarpment of South Africa. 7135 records from DMNS Egg Collection (Arctos). 495 records from USFWS Bee surveys - Sandbar WMA, VT 2018. 1 records from Happywhale - Layard's beaked whale in Southern Ocean. 45 records from Colección de moldes endocraneanos del CENPAT. 20 records from Biting midges of the tribe Ceratopogonini (Diptera: Ceratopogonidae) from the Middle East, with keys and descriptions of new species. 4 records from Two new sympatric species of Eusarsiella (Ostracoda: Myodocopida: Sarsiellidae) from the Florida Keys with a morphological phylogeny of Sarsiellinae. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 2290 records from Study on plankton at the port of Ostend in 1965. 6 records from Dactylobasis gen. nov. from Colombia, a new genus of Zygoptera with Teinobasini affinities (Odonata: Coenagrionidae). 41 records from Site Condition Monitoring of Annex II Vertigo species in Scotland. 162 records from Inventario forestal de una parcela permanente de restauración en el Parque Nacional Natural Alto Fragua Indi Wasi, en la vereda La Estrella, Caquetá. 20 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 2 records from Contribution to the genus Okinawepipona Yamane (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 9140 records from Relevés of Main Vegetation Types of the Prioksko-Terrasnyi Biosphere Reserve (2019-2020). 49 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 2 records from First description of the female of Clubiona milingae Barrion-Dupo, Barrion & Heong, 2013 (Araneae, Clubionidae). 239 records from Hidden in plain sight: reassessment of the pig-footed bandicoot, Chaeropus ecaudatus (Peramelemorphia, Chaeropodidae), with a description of a new species from central australia, and use of the fossil record to trace its past distribution. 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 1 records from First fossil Eccoptarthridae (Coleoptera: Curculionoidea) from the Mesozoic of China. 72 records from Amphibian and Reptile species occurrence records in the Tana River Basin, Kenya. 391 records from An updated checklist of aquatic plants of Myanmar and Thailand. 10471 records from A practical introduction to microbial molecular ecology through the use of iChips. 15 records from Review of the genus Pagastia Oliver (Diptera: Chironomidae: Diamesinae) from North America, with description of P. (P.) subletteorum sp. nov.. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 1 records from Registro de Chromolaena tacotana asociado al proyecto: Relación estructura-actividad anti-cáncer de flavonoides sobre líneas celulares cancerosas. 1641 records from BioGIS - Bryophytes - HUJ collections. 3 records from First description of the male of the easternmost Harpactea species, H. parthica (Araneae: Dysderidae). 36735 records from Future climate change affects the microbiome and condition of habitat-forming kelp. 175 records from The Brown University Foraminiferal Data Base (BFD). 958 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 55 records from Caracterización faunística de la Reserva Forestal Protectora Regional Brisas del Rincón. 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 867 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 34 records from National System of Protected Areas in Poland - Fungi. 2 records from Perscheloribates Paratzitzikamaensis N. Sp., With Supplementary Descriptions Of Scheloribates Elegans And Monoschelobates Parvus (Acari, Oribatida, Scheloribatidae) From Ecuador. 60 records from Pilzlehrwald. 1552 records from marine sediment metagenome Raw sequence reads. 30 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 487 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 776 records from Programme ACT : Répartition Pie bavarde 2010 - 2014 Coordonnées GPS Lambert 93. 4 records from Abundance of radiolaria at station UT99-5-1. 144 records from Données naturalistes de Xavier BONNET. 1 records from (Figure 8) Relative abundance of nannoliths at DSDP Hole 62-464. 330046 records from Broedvogels - Atlas of the breeding birds in Flanders 2000-2002. 3 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 43 records from Flora und Fauna in unserer Kita. 2 records from Synaptus iranicus sp. nov., a second species of the genus Synaptus Eschscholtz, 1829 from Iran (Coleoptera: Elateridae) discovered by an integrative approach. 1015 records from Programme ACT : Répartition Merle noir 2005 - 2009 Coordonnées GPS Lambert 93. 43 records from Abundance of coccosphere-units of sediment core GIK23424-3. 14 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 6 records from Free-living marine nematodes of Desmodorella and Zalonema (Nematoda: Desmodoridae) with description of two new species from the deep sea of the North Western Pacific. 8 records from New Polypheretima and Pithemera (Oligochaeta: Megascolecidae) species from the Mt. Malindang Range, Mindanao Island, Philippines. 15 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 3 records from Argiope hoiseni, a new species of the spider genus Argiope (Araneae, Araneidae) from Peninsular Malaysia based on morphology and molecular analyses. 3 records from Hagneia kallea gen. and sp. nov. (Hemiptera: Fulgoromorpha: Ricaniidae) from North Vietnam. 1244 records from Some finds of flora and fauna in Kharkiv region. 82 records from Taxonomic And Distributional Notes On Perlesta Teaysia, P. Golconda, And P. Shawnee (Plecoptera: Perlidae). 8 records from Reconsideration of the apterous carventine genus Crassocoris and description of Paracrassocoris gen. nov. from China (Hemiptera: Heteroptera: Aradidae). 130 records from Vamize and Ibo islands corals dry collection MHNM. 2442 records from Flore des Pyrénées. 40917 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 81532 records from Bob Merritt Coleoptera Dataset. 330 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 22 records from Taxonomic review of the plant bug subfamily Isometopinae for Taiwan and Japanese Southwest Islands, with descriptions of new taxa (Hemiptera: Heteroptera: Miridae: Isometopinae). 12 records from Happywhale - Indian humpback dolphin in Indian Ocean. 74 records from P. W. Lund collection in the National History Museum of Denmark, Copenhagen. 13768 records from Mise en place d'un suivi scientifique des rhopalocères pour la production d’indicateurs de biodiversité. 1043356 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 59 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 412606 records from DATAVES. 109 records from Projet Diable de mer - AILERONS. 114 records from Mamíferos no voladores de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 649 records from Beetles from nature reserves and nearby forests in Østmarka. 28 records from Caracterización de la fauna del páramo del Duende, litoral del San Juan, Chocó. 40 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera Oecophoridae) V. The unistriatella species group, with descriptions of seven new species. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 28 records from Systematic Notes On Kiotina Klapálek And Hemacroneuria Enderlein (Plecoptera: Perlidae), With Description Of Four New Species. 1 records from Redescription of Leptogyra bujnitzkii (Gorbunov, 1946) comb. nov., the first representative of the gastropod subclass Neomphaliones from the high Arctic. 11 records from Supplementary Illustrations For Two Nemoura (Plecoptera: Nemouridae) Species. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 19 records from Distribution Data for Megachile chomskyi. 337 records from Flora vascular y no vascular: expedición Monte y Pinal - Proyecto Boyacá BIO UPTC. 25771 records from Berea College, Ralph L. Thompson Herbarium. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1012 records from Programme ACT : Répartition Merle noir 2011 - 2015 Coordonnées GPS Lambert 93. 175 records from A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 3. Revision of the Craspedophorus strachani and C. brevicollis groups (Coleoptera: Carabidae). 401 records from Distribution of nanoplankton at trap WR2. 54 records from Taxonomic studies on Dolichothrips (Thysanoptera: Phlaeothripinae), pollinators of Macaranga trees in Southeast Asia (Euphorbiaceae). 3 records from A new species of Xiphogramma Nowicki (Hymenoptera: Chalcidoidea) from Saudi Arabia. 15 records from A review of the Blaesiina (Coleoptera, Scarabaeidae, Cetoniinae, Gymnetini). 4518 records from Données d'observation de la mégafaune marine issues des campagnes océanographiques en France métropolitaine. 616 records from Flora vascular y no vascular:expedición El Consuelo - Proyecto Boyacá BIO UPTC. 382 records from Chronicle of Nature - Phenology of Plants of Bryansk Forest Nature Reserve. 3 records from Oxynoemacheilus shehabi, a new nemacheilid loach from the upper Orontes in southern Syria (Teleostei: Nemacheilidae). 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 141796 records from Fermanagh Flora. 96 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 8 records from Marine metagenome ICM_AGW. 15306 records from Macrophyte Lake Data. 2 records from Gastrodia madagascariensis (Gastrodieae, Orchidaceae): from an historical designation to a description of a new species from Madagascar. 78 records from Données de la naturaliste Anna Even. 11 records from Happywhale - Peale's Dolphin in South Atlantic Ocean. 2512 records from Données du Busard de Maillard (Circus maillardi) du Parc national de La Réunion. 3540 records from Siliceous microfossil occurrence, Site 177-1091. 5 records from On the genus Aphaobius Abeille de Perrin, 1878, with description of a new species from the mesovoid shallow substratum (MSS) of Austria (Coleoptera: Leiodidae: Cholevinae: Leptodirini). 814 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 1 records from Taxonomic re-evaluation of the monotypic genus Pararhabdophis Bourret, 1934 (Squamata: Colubridae: Natricinae) with discovery of its type species, P. chapaensis, from China. 464 records from Colección Herpetológica-Museo de Historia Natural Unillanos. 3 records from Range table from benthic foraminifers in ODP Hole 149-900A. 1 records from On the Chilopoda from Turkey. 4 records from Proposal of Marbefia, gen. n. and Inermiphonte, gen. n., including updated keys to the species of Pseudonychocamptus Lang, 1944 and Paralaophonte Lang, 1948 (Copepoda, Harpacticoida, Laophontidae). 145 records from Revision of Telothyria van der Wulp (Diptera: Tachinidae) and twenty-five new species from Area de Conservación Guanacaste in northwestern Costa Rica with a key to Mesoamerican species. 3 records from A new species of Gymnophthalmus (Squamata: Gymnophthalmidae) from sand dunes of the Llanos of Apure, Venezuela. 68 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 87 records from Kystfuruskoger i Tysnes og Fusa. 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 407 records from Systematics, biogeography and host-plant relationships of the Neotropical jumping plant-louse genus Russelliana (Hemiptera: Psylloidea). 61 records from Diatom abundance of Hole 95-613. 61701 records from UCLA Donald R. Dickey Bird and Mammal Collection. 2364 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 7 records from Die Bachspezies 2008/2009. 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 13 records from Two new species and a key to the dustywings of Mexico (Neuroptera, Coniopterygidae). 4 records from Haematophagous biting midges of the extant genus Culicoides Latreille (Diptera: Ceratopogonidae) evolved during the mid-Cretaceous. 5 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 2334 records from University of Vermont, Pringle Herbarium, Algae Collection. 17 records from Abundance of benthos infauna at station GIK23042-2. 63 records from Streuobstwiese. 15 records from Description of lithologic section units of IODP Hole 325-M0041A. 197 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 16 records from Revision of the euryglossiform species of the Afrotropical bee genus Scrapter Lepeletier & Serville, 1828 (Hymenoptera: Apoidea: Colletidae). 19619 records from Carabidae of the Carpathians. 23 records from The Phalacridae (Coleoptera, Cucujoidea) of Canada: new records, distribution, and bionomics with a particular focus on the Atlantic Canadian fauna. 2589 records from 1848-1982 Lundy Field Society The Marine Fauna of Lundy. 80 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 237 records from Flora vascular y no vascular: expedición Cuenca Media del río Chicamocha - Proyecto Boyacá BIO UPTC. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 8 records from An overview of Scirtidae (Coleoptera) described by Antoine Joseph Jean Solier (1792 - 1851). 2608545 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 15883 records from Canadian Lakes Loon Survey. 7 records from Two New Species of Composetia (Annelida: Nereididae) from Small Estuaries in the Ryukyu Islands, Southern Japan, with a List of All Species Currently Belonging to Composetia. 13 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1009 records from Programme ACT : Répartition Merle noir 2012 - 2016 Coordonnées GPS Lambert 93. 591 records from Alan Wormington Collection. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 58 records from Taxonomic novelties in Apocynaceae subfam. Asclepiadoideae from New Caledonia. 33385 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 246 records from Protistan plankton diversity along salt gradient. 5 records from Revalidation of a moray eel, Gymnothorax mucifer Snyder, 1904 (Teleostei: Anguilliformes: Muraenidae), with a revised distribution. 4567 records from Inventaire de la flore du Grand Poitiers 2009. 59823 records from Polish gene bank – passport data of plants accessions which are important in human life. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1513 records from M. Gollop Collection. 4333 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 16583 records from SMDB - Santa Maria Departamento de Biologia. 1 records from Données naturalistes d'Olivier DELZONS. 53418 records from Naturalis Biodiversity Center (NL) - Diptera. 8 records from The genus Thoradonta in Thailand (Orthoptera: Tetrigidae: Scelimeninae) with description of two new species. 3 records from New species of Myrmicine ants from Western Australia (Hymenoptera: Formicidae). 6 records from Review of the enigmatic genus Boalda with transfer of pulcherrima Köhler from Nephelistis and description of two new species (Lepidoptera: Noctuidae). 2 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 74 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/508-22. 1 records from A New Species Of The Genus Liophloeothrips (Thysanoptera, Phlaeothripidae) From Iran. 4 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 154 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 445 records from Propuesta de diagnóstico, erradicación y monitoreo post-erradicación, de especies exóticas invasoras en oasis de Baja California Sur, centrándose en las dos más relevantes: rana toro Lithobates catesbeianus y manto de cristo Cryptostegia grandiflora. 7122 records from Whale catches in the Southern Ocean. 9 records from On the identity of the Palearctic species of the wolf spider genus Trebacosa (Araneae: Lycosidae). 406 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 8 records from Revision of the ant genus Anillomyrma Emery, 1913 (Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 6 records from A new Synbranchus (Teleostei: Synbranchiformes: Synbranchidae) from ilha de Marajó, Pará, Brazil, with notes on its reproductive biology and larval development. 14860 records from Floristic diversity of the protected areas of Mont Kouffé and Wari Maro in the north of Benin. 7 records from A new crayfish of the genus Cambarus Erichson, 1846 (Decapoda: Cambaridae) from an under-sampled habitat type in central Ten- nessee, USA. 124 records from Mycoblitz 2017 - IRBV et Cercle des Mycologues de Montréal. 481 records from FernsDarwinCore. 12 records from Grupo de Macroinvertebrados de la laguna Cristalina Páramo de la Rusia-Boyacá.. 45548 records from The Taiwan Roadkill Observation Network Data Set.. 222 records from Taxonomic revision of the Neotropical genus Ormiophasia Townsend, 1919 (Diptera: Tachinidae), with the description of eight new species. 218 records from Données naturalistes de Ingénieurs écologues GEREA. 124 records from Distribution And New Records Of Lymexylidae (Coleoptera: Lymexyloidea) In Guatemala And Mexico. 4523 records from sediment metagenome Metagenome. 1158 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 5 records from Revision of the genus Sinobathyscia Perreau (Coleoptera, Leiodidae, Cholevinae) from China, with description of a new species. 685 records from AMAPPS Northeast Aerial Cruise Summer 2010. 3 records from First record of the genus Eriopisella Chevreux, 1920 (Crustacea, Amphipoda, Senticaudata, Eriopisidae) from Australia, with the description of a new species, Eriopisella moretoni sp. nov.. 29596 records from University of California Santa Barbara Invertebrate Zoology Collection. 32 records from Two new species of Nullana from southern Brazil (Hemiptera: Cicadellidae: Gyponini) with key to males. 26 records from Shallow-water Ascidians from Matua Island (central Kuril Islands, NW Pacific). 2227 records from IRAD Cameroon insect collection. 1156 records from The Reduviidae (Hemiptera: Heteroptera) of Alabama, with a morphological key to species. 611 records from Occurrence of bird species along Loduare - Golini Road, Ngorongoro Conservation Area, Arusha, Tanzania. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 427 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 9 records from Redescription of Isotoma grana Lee, Kim & Kim, 1993 and description of a new species of Isotoma Bourlet, 1839 (Collembola: Isotomidae) from Korea. 141 records from Nannofossil abundance of Hole 94-610B. 3 records from A new species of planthopper in the genus Myxia (Hemiptera: Auchenorrhyncha Cixiidae) from the Reserva Privada el Silencio de Los Angeles Cloud Forest in Costa Rica. 3 records from Hoya rotundiflora (Apocynaceae, Asclepiadoideae), a new horticulturally important species from Myanmar. 20005 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 5222 records from 台灣花蓮沿海賞鯨活動鯨豚觀測紀錄 (The observation records from the activities of whale and dolphin watching in the offshore of Hualien, Eastern Taiwan). 1 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 61 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 6390 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 9 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 10 records from New genus, new species and new records in Lamiinae (Coleoptera, Cerambycidae). 142 records from Hartland Nature Club Lepidoptera Collection. 117177 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 9 records from Xenosinelobus balanocolus, a new tanaidid genus and species (Crustacea: Peracarida: Tanaidacea) from barnacles on intertidal rocky shores and seawalls in the Singapore Strait. 136538 records from Fish specimens of Kagoshima University Museum. 245 records from A revision of Colletes Latreille (Hymenoptera: Colletidae: Colletinae) from Brazil, Paraguay and Uruguay. 13364 records from UTEP Invertebrates (Arctos). 4182 records from Diptera Collection of Museum and Institute of Zoology PAS. 11 records from Notes on the first instar larvae of the genus Tipula (Diptera: Tipulidae). 1308 records from Fish occurrence in Kuban River basin. 107 records from Revision of the Traumatomutilla gemella species-group (Hymenoptera, Mutillidae) with the description of its hitherto unknown males. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 5 records from A new skink of the genus Scincella Mittleman, 1950 (Squamata: Scincidae) from Ba Den Mountain, Tay Ninh Province, southern Vietnam. 163 records from Relative abundance of coccosphere-units at site GIK23414. 691 records from Tentaculata collection of National Museum of Nature and Science. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 4 records from The genus Aivalykus Nixon, 1938 (Hymenoptera: Braconidae: Doryctinae) with description of a new species from India and Arabian Peninsula. 766242 records from AMNH Bird Collection. 21 records from New species of Phaloria (Orthoptera: Phalangopsidae: Phaloriinae) from West Papua (Indonesia). 2721 records from Données du/de la naturaliste Chevallier Laurent provenant de la base de donnée du SINP Île-de-France CETTIA. 174 records from UNCW Norfolk Canyon Aerial Survey - Left side - 2016. 3564 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 27 records from Lioscorpius trifasciatus, a new scorpionfish (Scorpaeniformes: Setarchidae) from the South-West Pacific Ocean.. 60 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 884 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 59 records from Seven new giant pill-millipede species and numerous new records of the genus Zoosphaerium from Madagascar (Diplopoda, Sphaerotheriida, Arthrosphaeridae). 5 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 4 records from A new diurnal gecko in the genus Gonatodes (Squamata: Sphaerodactylidae) from the foothills of the Serranía de San Lucas, Norosí-Colombia. 580 records from DOW-2. 65 records from Taxonomic revision of Ceropegia sect. Huernia (Asclepiadoideae, Apocynaceae) in Saudi Arabia with three new combinations. 6 records from Redescriptions of three species of Pulvinaria (Hemiptera: Coccomorpha: Coccidae) in Japan. 30 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 1682 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 1 records from Happywhale - Green Sea Turtle in North Pacific Ocean. 8 records from Nannofossil abundance of Hole 10-93. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 2996 records from MMS Seabird Ecology Study 1985. 1422 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 2044 records from BioBlitz Barcelona 2010-14. 9 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 43 records from Revision of the Agrilus gratiosus species-group (Coleoptera, Buprestidae, Agrilinae). 38 records from Ours 2006 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 2204 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 50 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 23 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 249887 records from Phase 2 Lowland Grassland Survey of Wales. 2 records from Review of subterranean Quedius, with description of the first hypogean species from the Russian Far East (Coleoptera: Staphylinidae: Staphylinini). 123 records from Bryological collection of Yugra State University. 27 records from Bemerkenswerte Faltenwespen aus der äthiopischen Region. Teil 14 (Hymenoptera, Vespidae, Eumeninae). 276479 records from hymenoptera. 39 records from (Table 1) Middle Eocene silicoflagellates from DSDP Hole 95-612. 1086 records from FFH-Gebiet "Calwer Heckengäu". 372 records from Amphibian and Reptilian (KIEE-AR). 460 records from pteri4t2017. 2155 records from PCE/TCE dechlorinating microbial community and dehalogenase genes from Wonju Stream, South Korea. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 3286 records from Plant specimens of Nasunogahara Museum. 230 records from Biometría peces Parque Nacional Natural La Paya. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 95 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 1925 records from Análisis de Integridad Biológica en la Reserva Forestal Protectora Regional Bitaco. Convenio CVC- Univalle 108 de 2017. 12 records from New or rare Madagascar tiger beetles- 20. Pogonostoma (Bathypogonum) horimichioi sp. nov. and supplemented characters of P. (B) levigatum levigatum (W. Horn) and P. (B.) levigatum lucens Rivalier (Coleoptera: Cicindelidae). 13846 records from Données faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 3 records from New early Pleistocene Alligator (Eusuchia: Crocodylia) from Florida bridges a gap in Alligator evolution. 4 records from Benthic macrofauna abundance of sediment core 13077-063. 24 records from Taxonomic revision of Australian Amobia Robineau-Desvoidy, 1830 (Sarcophagidae: Miltogramminae): integrating morphology and genetics finds a new species and tackles old problems. 1657 records from Diatomeas bentónicas de los oasis de Baja California Sur. 4571 records from WII Herbarium Dataset. 53 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 9 records from Peyerimhoffia jaschhoforum (Diptera, Sciaridae), a new deadwood inhabiting species from Canada. 36171 records from Quaid-i-Azam University Herbarium. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 728 records from (Table 4) New palynological record of sediments from Odderade. 18 records from Anfibios presentes en el Cerro Jánano. 7230 records from Protist Diversity in the East China Sea. 119 records from Données espèces - Expertise IPE 79. 1711573 records from NBIS Records to December 2016. 64 records from Carrion beetles (Coleoptera, Silphidae) of Volga-Kama Nature Reserve. 172 records from Nezara viridula records held by the Royal Horticultural Society. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 294 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1499 records from Structures and Nutrition Requirements of Macrozoobenthic Communities in the area of the Lomonossov Ridge, 1995-1998. 789 records from Occurrence of insect species along Loduare - Golini Road, Ngorongoro Conservation Area, Arusha, Tanzania. 774 records from South American Antarctic Marine Biodiversity Literature. 1 records from Redescription of Corydoras guapore Knaack, 1961 (Siluriformes: Callichthyidae), a midwater Corydoradinae species from the rio Guaporé basin. 7 records from Inventario de Murciélagos en la Finca la Reserva, El Perico, Yopal, Casanare. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 14496 records from A grid database on vascular plant distribution in the Meshchersky National Park, Ryazan Oblast, Russia. 81 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 37 records from Blue Mountains Swamp Archaea. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 8 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 3 records from Species status of Colias misti (Pieridae: Coliadinae) from the Arequipa region South Peru, and a description of its new subspecies, from Cotahuasi canyon South-Central Peru. 4 records from Happywhale - in South Atlantic Ocean. 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 4418 records from California State University, Long Beach Birds. 1374 records from Epiphytic mosses from the northwest Iberian quadrant (Spain). 1926 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 18 records from Thirteen new records of ferns from Brazil. 713 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 30621 records from ASE herbarium - Universidade Federal de Sergipe - Herbário Virtual REFLORA. 114 records from Marine metagenome ICM_AWP. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 550 records from SOCAL FZN4 Marine Mammal Aerial Monitoring 2013. 25 records from Colecta de plantas pertenecientes a la familia Cactaceae, enmarcadas en el proyecto: Dilucidación de la sistemática de los géneros de la familia Cactaceae. 26 records from Occurrence of mammalia relicts at site Sveduv stul. 194545 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 71042 records from FKSE-Herbarium of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 6 records from A new Dondice Marcus Er. 1958 (Gastropoda: Nudibranchia) from the Mediterranean Sea reveals interesting insights into the phylogenetic history of a group of Facelinidae taxa. 10 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 9 records from Molecular circumscription of new species of Gyrocotyle Diesing, 1850 (Cestoda) from deep-sea chimaeriform holocephalans in the North Atlantic. 6 records from Three new species of trigonopoid Platynotina (Tenebrionidae: Pedinini) from the Baviaanskloof Nature Reserve, South Africa. 332 records from Colección de chinches (Insecta: Hemiptera) del Centro de Colecciones Biológicas de la Universidad del Magdalena. 24 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 4 records from Mycale (Aegogropila) antiae sp. nov. (Demospongiae; Poecilosclerida; Mycalidae) from Galicia (NW Iberian Peninsula). 1 records from Registro de Ateles belzebuth (mono araña) en el municipio de Yopal, departamento de Casanare. 23524 records from RNF - Données du Conservatoire d'espaces naturel Franche-Comté. 1814 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 510 records from Deep-sea meiobenthos at Calvi (Corsica) sampled in September 1982. 98 records from Données opportunistes sur les odonates. 347 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 1 records from A new species of the genus Nenasa (Hemiptera: Fulgoroidea: Caliscelidae) from mainland China. 74729 records from Synthèse 10x10km de la faune sauvage des Directives Oiseaux et Habitats-Faune-Flore recensée via les portails gérés par la LPO de 2013 à 2017. 70 records from The Brazilian Goblin Spiders Of The New Genus Predatoroonops (Araneae: Oonopidae). 16760 records from Données Entomologiques A. HORELLOU 1988-2018. 80 records from The Pyraloidea (Lepidoptera) fauna of the woody savannah belt in Mali, West Africa. 284 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 5 records from A new micropterous winter species of Leuctra (Plecoptera: Leuctridae) and little known endemic stoneflies from the Greater Caucasus. 7 records from Тaxonomic position of Orthochirus olivaceus (Karsch, 1881), the type species of the genus Orthochirus Karsch, 1892 (Scorpiones: Buthidae). 53 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1895 records from Données opportunistes amphibiens-reptiles du Nord et du Pas-de-Calais. 1536 records from Records of Halicarcinus planatus at sub-Antarctic regions. 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 56 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 30 records from Nannofossil abundance of Hole 20-199. 353 records from MGC Herbarium of University of Malaga (Spain): MGC-Lichen dataset. 91 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 159 records from Données espèces - Expertise IPE 37. 394 records from Nannofossil abundance of Hole 74-528A. 11797 records from WOLL AVH data. 6 records from On the Chilopoda from Turkey. 12628 records from Recensement des espèces en vue de l'élaboration du répertoire des forêts sacrées, forêts galeries, savanes et autres formation floristique du Bénin.. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 2 records from A new species of leaf-toed gecko (Phyllodactylidae, Phyllodactylus) from Maria Cleofas Island, Nayarit, Mexico. 2 records from Taxonomy of the Oriental leafhopper genus Parabolopona (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) with a new species from China. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 83 records from Ostracoda abundance of Hole 48-403. 154 records from Shannon Index and species richness for arthropods. 50 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 3 records from Latheticomyia Wheeler (Diptera: Pseudopomyzidae) from Peru: new species, description of the male of L. longiterebra Hennig and a key to species. 3543 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 148 records from SOVIET ANTARCTIC EXPEDITIONS for Zooplankton (R.V. OB March-May 1956, January-March 1957;R.V.ACADEMIC KURCHATOV, October 1971-January 1972; RV DMITRY MENDELEEV;R.V.ACADEMIC IOFFE 1992).. 67 records from Monitoreo de la ocupación del Oso de antejoso (Tremarctos ornatus) en el Parque Nacional Natural Las Hermosas Gloria Castaño de Valencia para 2017 y 2018. 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 2718 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 2563 records from Phenological Center - Plants (Laplandskiy). 159 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 2 records from Benthic foraminifera abundance of Hole 84-567A. 101 records from Urwald 1 (Bad Waldsee). 359799 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 7 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 35 records from Revision of the genus Neozavrelia Goetghebuer, Thienemann, 1941 (Diptera Chironomidae) from Eastern Siberia and the Russian Far East, with the description of new species. 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 13 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 129 records from Species of the bee genus Centris Fabricius, 1804 described by Heinrich Friese (Hymenoptera: Apidae). 16 records from Hazel Dormouse in Ireland. 12 records from Three new cave species of the subgenus Tachycines (Gymnaeta) (Orthoptera Rhaphidophoridae: Aemodogryllinae) from northern Guizhou, China. 34 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 13822 records from Flora of the Korean Peninsula. 2 records from A new country record of Raorchestes cangyuanensis Wu, Suwannapoom, Xu Murphy & Che 2019 and additional record of Kurixalus yangi Yu, Hui, Rao & Yang 2018 (Anura: Rhacophoridae: Rhacophorinae) from India. 348 records from Antarctic pycnogonids. 62213 records from MLZ Bird Collection (Arctos). 14 records from Coleoptera identified from the Hornchurch Marshes site, Dagenham, London. 14 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 6 records from 2. Donauinsel bei Entau. 2 records from Happywhale - False Killer Whale in South Atlantic Ocean. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 186 records from Taxonomic revision of the Neotropical genus Himantigera James, 1982 (Diptera: Stratiomyidae: Sarginae), including the description of two new species and a key to the known species. 4 records from Coeliccia lecongcoi sp. nov., a new damselfly from the Central Highlands of Vietnam (Odonata: Zygoptera: Platycnemididae). 5 records from DREAL_PACA_-_N2000_-_Office_National_des_Forêts_04_2017_12_18. 8800 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 1318 records from Ornithologie Federsammlung - SNSD. 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 39 records from Northern Cyprus 2010 (aggregated per 1-degree cell). 2 records from Perotrochus caledonicus (Gastropoda: Pleurotomariidae) revisited: descriptions of new species from the South-West Pacific. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 412 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 45 records from Liether Park (LMS), 5a. 2 records from Review of the species of Anastatus (Hymenoptera: Eupelmidae) known from China, with description of two new species with brachypterous females. 12847 records from Midden-Limburg Fish Ponds Survey. 88702 records from Herbarium (ICEL). 108468 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 1 records from Zetes ephippiatus. 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 15235 records from Leiner-Herbar Konstanz. 3 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 1567 records from AMAPPS Northeast Aerial Cruise Summer 2016. 895 records from Geometridae de France métropolitaine. 105 records from bmhs_moth_collection. 256 records from Cactophilic Drosophila and Opuntia. 20 records from A revision of the genus Navasoleon Banks (Neuroptera: Myrmeleontidae: Nemoleontini). 4 records from Limnebius (Limnebius) agnieszkae sp. n. from the Crimean Peninsula (Coleoptera: Hydraenidae). 22624 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 232 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 2 records from Umbellula pomona sp. nov., a new sea pen from Mar del Plata Submarine Canyon (Cnidaria: Octocorallia: Pennatulacea). 763 records from SEFSC GoMex Oceanic 1993 (W). 30425 records from WCPS Bird Survey Project. 106 records from Sylter Meerstrandläufer. 77 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/587-14. 237 records from Taxonomic review of the genus Dascillus Latreille, 1797 in the Western Palaearctic (Coleoptera: Dascillidae). 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 8 records from Complementary description of Podocinella misella (Berlese, 1913) (Acari: Podocinidae) and a key to world species of the genus. 37950 records from Fungal occurrences from the Basque Country and neighbouring areas: ARAN-Fungi. 1380 records from Plant observations from Białowieża National Park. 1020 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 1290 records from Diversity of Spiders from Azorean Trails. 12345 records from United Kingdom National Whale Stranding Database 1913-2008. 4084 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 10219 records from Inventaire de la flore de Charente-Maritime 2018. 1996 records from Pollen profile RAC20, Lake Racou, France. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 3 records from Some new brachypterous cockroaches (Blattodea: Blaberidae: Epilamprinae) from the Philippines. 9150 records from NEON Biorepository Carabid Collection (DNA Extracts). 219 records from Tillegg Røtinga i Os. 44 records from Oman 2008: Olive Ridley Turtles of Masirah (aggregated per 1-degree cell). 28 records from Données naturalistes de Franck MERLIER. 3 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 17 records from Characterization of Microbial Community Structure and Population Dynamics of Tetrachloroethene-Dechlorinating Tidal Mudflat Communities using a Multipronged Approach. 9201 records from Survey data of tidal flats on the Monitoring sites 1000 project, BDCJ. 10898 records from Inventario de Hymenóptera; parasítica en México. 3 records from A new species of the genus Cyparium from northern Sulawesi, Indonesia (Coleoptera: Staphylinidae: Scaphidiinae). 2821 records from UAM Herbarium (ALA), Algae Collection (Arctos). 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1 records from A new genus of mongoliulid millipedes from the Far East of Russia, with a list of species in the family (Diplopoda, Julida, Mongoliulidae). 1156 records from 3Soil16S. 2 records from New and interesting palpigrades (Arachnida, Palpigradi) of the genera Koeneniodes Silvestri, 1913 and Prokoenenia Börner, 1901 from Asia. 60094 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 2555 records from Données de la structure ANCA (les Amis Naturalistes des Coteaux d'Avron) provenant de la base de donnée du SINP Île-de-France CETTIA. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 53 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 4 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 24 records from Nannofossil abundance of Hole 24-233A. 470 records from Gross body measurements of Laternula elliptica collected from sites adjacent to Casey Station 2014/15. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 1 records from Dinoflagellate abundance of Hole 28-274. 9 records from The identity of Aplocheilus andamanicus (Köhler, 1906) (Teleostei: Cyprinodontiformes), an endemic Killifish from the Andaman Islands, with notes on Odontopsis armata van Hasselt. 10 records from Multiple lines of evidence reveal a new species of Krait (Squamata, Elapidae, Bungarus) from Southwestern China and Northern Myanmar. 24 records from Occurrence of mammalia relicts at site Biedermann. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 14997 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 13 records from Synonymies, new records, and new species in Cerambycinae (Coleoptera Cerambycidae). 232 records from Monitoreo biológicos en la cuenca Frayle, ARA - RARE - CVC – Asociación Calidris. 551 records from SWFSC Marine Mammal Survey, Vaquita 1997, Cruise 1608. 265878 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 3 records from One new species of the subgenus Xizicus (Zangxizicus) (Orthoptera: Tettigoniidae: Meconematinae) from China. 5 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 408 records from Birds Specimens of Akita Prefectural Museum. 12 records from Urochordeumatidae Silvestri, 1909, a millipede family endemic to Washington State, USA (Chordeumatida, Striariidea, Striarioidea). 2191 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Crustáceos). 102 records from Données du naturaliste JAPIOT Xavier provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 101 records from Données naturalistes de LE GLOANEC Vincent. 136 records from Oberes Schindelbachtal. 84 records from SNH Invertebrate Site Condition Monitoring 2015: Dunhog Moss SSSI. 213433 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-81. 141894 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 3 records from Review of Campsicnemus species from the Atlantic Ocean Islands (Diptera: Dolichopodidae). 8363 records from Colección de Bruniales, Buxales, Canellales y Caryophyllales del Museo Botánico CORD - IMBIV. 588 records from Agroforestry plant species found in protected areas and riparian lands in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 1027 records from Programme ACT : Répartition Merle noir 1996 - 2000 Coordonnées GPS Lambert 93. 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 11 records from Revision of the Ulopinae leafhoppers (Hemiptera: Cicadellidae) of the Indian subcontinent, I. Ulopini genera: Daimachus, Radhades and Ulopsina. 2 records from Taxonomy of Oncaeidae (Copepoda, Poecilostomatoida) from the Red Sea. V. Three species of Spinoncaea gen. nov. (ivlevi-group), with notes on zoogeographical distribution. 423 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 445 records from There are 3 zooplankton samples from 3 different ponds, we collected sample and use the fresh samples to do DNA extraction directly, then mix them with adjustment guided by the number of species within each of them. At last, use Hiseq-2599 PE-150 to do NGS work. 1 records from New genus and species of the family Niphargidae (Crustacea: Amphipoda: Senticaudata), Chaetoniphargus lubuskensis gen. nov., sp. nov. from Croatia. 43 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 45 records from An der Ohm, (Wettsaasen). 16 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 5 records from A revision of the genus Saccoglossus (Hemichordata: Enteropneusta: Harrimaniidae) with taxonomic descriptions of five new species from the Eastern Pacific. 477 records from Philippine Mollusk Symbiont - ICBG Collection. 185 records from Inventaire des odonates d'intérêt communautaire. 4 records from Two new species of heavily calcified cyclostome bryozoans from the intertidal of Akkeshi Bay, Hokkaido, Japan. 3 records from Manx Basking Shark Watch 2017-2018 (aggregated per 1-degree cell). 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 6 records from The Lanternfly genus Polydictya (Hemiptera: Fulgoromorpha: Fulgoridae) from Sulawesi and neighbouring islands, with the description of three new species. 168 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 2112 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 27 records from Taxonomic study of the genus Promalactis Meyrick (Lepidoptera, Oecophoridae) from Hainan Island, China (III). 2322 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 1798 records from Insect (KIDR-IN). 635 records from Distribución, estructura poblacional y variación genética de algunas especies de pinos en peligro de extinción en México. 1014 records from Programme ACT : Répartition Merle noir 2009 - 2013 Coordonnées GPS Lambert 93. 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 11393 records from marine metagenome Metagenome. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 1 records from Radiolaria assemblage in sediment core GIK23400-3. 65 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 259 records from Programme ACT : Répartition Alouette lulu 2009 - 2013 Coordonnées GPS Lambert 93. 77 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1a. 104 records from Kirkliston Range stream monitoring. 21296 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 115 records from Israel Sea Turtle Tracking Project 2008: Loggerhead & Green Turtles (aggregated per 1-degree cell). 5 records from Morphological and molecular characterisation of Discotylenchus lorestanensis sp. n. (Nematoda: Tylenchidae) from Iran. 6 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 344 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 62 records from Sibojaï_2017_12_18. 179 records from Ictiofauna de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 355 records from Meetnetten.be - Fyke counts for Amphibia in Flanders, Belgium. 277 records from Inventaire de la faune malacologique de la Réserve naturelle des gorges de l'Ardèche (2002). 25446 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 18 records from HRC SCC Vessel-Based Monitoring Surveys February 2010. 37479 records from Abondances et caractéristiques biologiques des juvéniles de saumons échantillonnés lors des indices d'abondance du saumon dans la rivière Scorff (France). 6629 records from Los mamíferos del estado de Durango, México. 2239 records from Shotgun metagenomic analysis of Lake Paajarvi sediment microbes.. 14 records from A taxonomic review of the genus Acanella (Cnidaria: Octocorallia: Isididae) in the North Atlantic Ocean, with descriptions of two new species. 4 records from ALLIUM (AMARYLLIDACEAE) SPECIES IN PAKISTAN: TWO NEW RECORDS AND A NEW SPECIES FROM ZHOB (BALOCHISTAN). 75 records from Happywhale - Bryde's whale in South Atlantic Ocean. 104745 records from MSB Fish Collection (Arctos). 13 records from A contribution to the taxonomy of Anthaxia (Cratomerus) (Coleoptera Buprestidae: Anthaxiini) of East Africa. 21032 records from TPWD HARC Texas Coastal Fisheries Lower Laguna Madre Gill Net. 36 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 330 records from Langes Tannen (Uetersen). 121 records from Registros de dípteros asociados al proyecto: Estratificación espacial del dengue basado en la identificación de factores de riesgo en el departamento del Cauca. 186 records from Content of different diatom species in sediment core GIK23259-2. 4872 records from Microbial diversity of marine sediments. 2221 records from Churchyards for London. 21 records from A new genus of Theraphosid spider from Mexico, with a particular palpal bulb structure (Araneae, Theraphosidae, Theraphosinae). 8 records from Aktion des Romain-Rolland-Gymnasiums. 6 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 5 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 26 records from Four new species of Psychomyia (Trichoptera: Psychomyiidae) from China, with re-descriptions of two species. 36 records from The Trichoptera of Panama XIII. Further new country records for caddisflies (Insecta: Trichoptera) from the Republic of Panama. 710 records from Chronicle of Nature - Phenology of Fishes of Sikhote-Alin State Nature Biosphere Reserve Named After K. G. Abramov. 3 records from A new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Tamil Nadu, Southern India. 52 records from Anfibios presentes en las lagunas del municipio del Medio Baudó. 454 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 6 records from New species and records of the pseudoscorpion genus Geogarypus (Pseudoscorpiones: Geogarypidae) from India, Sri Lanka and New Guinea. 1169 records from Edible Insects Collection of the Natural History Museum Bulawayo (NMZB), Zimbabwe Occurrence dataset. 19 records from A new species and new records of Oocyclus Sharp, 1882 (Coleoptera: Hydrophilidae) from Brazil. 55 records from Integrative taxonomy of Thalerosphyrus Eatonı 1881 (Ephemeropteraı Heptageniidae) in Thailand. 343 records from Observations de cétacés à partir de navires de pêches: campagnes PETRACET/PROCET et OBSMAM - Observatoire PELAGIS. 11 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 11 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 3 records from Happywhale - Rough-toothed Dolphin in South Atlantic Ocean. 5 records from A new species of Ashlockobius (Heteroptera: Rhyparochromidae: Myodochini) from Venezuela. 1 records from Diagnosies provisoires de quelques espèces nouvelles de fourmis de Madagascar, récoltées par M. Grandidier.. 24 records from Four new species of Paranaitis Southern, 1914 (Phyllodocidae, Annelida) from southern and southeastern Brazil. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 5 records from A new species of Hemigrammus Gill 1858 (Characiformes: Characidae) from the upper Rio Negro, Amazon basin, Brazil. 1263 records from Banco de Germoplasma de Especies Nativas del Instituto de Ecologia y Ambiente Humano - UNSA- Arg. 84 records from Marine algal (seaweed) flora of Faial Island, Azores. 123 records from City of Edinburgh Natural Heritage Service - Hillend Wildflower Meadow Survey. 283 records from North Carolina Aquarium at Pine Knoll Shores Sea Turtle Awareness (aggregated per 1-degree cell). 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 2417 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 26 records from Korean Plant Virus Database. 1877 records from Odonata de la huasteca potosina (insecta). 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 1982 records from Pelagic sediment metagenome of Gulf of Kutch. 250 records from Colección de helechos de la FML. 116 records from Deep-sea (> 1000 m) Goniasteridae (Valvatida; Asteroidea) from the North Pacific, including an overview of Sibogaster, Bathyceramaster n. gen. and three new species. 22 records from A new species and four new records of Diduga Moore (Lepidoptera, Erebidae Arctiinae) from Thailand. 175 records from PSUZC-Rodents Collection. 3 records from Zoology in the Middle East. 4 records from Two new species of Parandrinae (Coleoptera: Cerambycidae) in the genera Parandra and Acutandra from South America. 109 records from Données naturalistes de Mr MONTAGNER Sylvain. 24 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 68884 records from Données de l'Observatoire de la Faune de Bourgogne. 21 records from The Oribatid Family Phthiracaridae III. Redescription of Phthiracarus nitens (Nicolet). 1 records from First description of the male of Oxythrips tristis Bagnall (Thysanoptera: Thripidae). 255 records from Programme ACT : Répartition Perdrix rouge 2009 - 2013 Coordonnées GPS Lambert 93. 1013 records from Monitoreo de aves en la zona del Anchicaya (Colombia, Valle del Cauca, Buenaventura) en el marco del Convenio de Investigación Icesi/Celsia. 2289 records from Marine Non Native Species records from Natural Resources Wales (NRW) Monitoring Research and Ad-hoc Sightings. 48 records from Identification of Important Turtle Areas for green turtles in the Sulu Sulawesi Marine Ecoregion (aggregated per 1-degree cell). 16 records from Phenological Center - Fishes (Murmansk). 245 records from Small rodents trapped in old growth forest in Vegårshei, Norway. 1295 records from martius-munchen-infocomp. 1 records from A new species of the genus Humphaplotropis from China (Orthoptera: Pamphagidae, Pamphaginae). 338 records from Comunidad fitoplanctónica presente en la Bahía de Buenaventura 2018. 47 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 54 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 10 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 7 records from New records of eriophyoid mites from Iran (Acari: Trombidiformes: Eriophyoidea) and a description of a new Brevulacus Manson species. 228 records from Visual Plants (144.41.33.158) - Plants from Costa Rica; Helmut Dalitz. 1889 records from Modelaje de la Distribución geográfica de Pinus pseudostrobus y P. leiophylla. 18 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 174 records from BIRDRACE Bon(n)apartemöwen. 3 records from Two new species and the molecular phylogeny of eight species of Macrostomum (Platyhelminthes: Macrostomorpha) from southern China. 2214 records from SANT-Bryo. 23 records from New species of the genus Aztecatopse Haenni & Huerta from Mexico (Diptera, Scatopsidae). 531 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 17 records from Plant-parasitic nematodes of Republic of Karelia. 2 records from Taxonomic notes on the genus Hydrobaenus with description of H. simferopolus sp. nov. from Crimea (Diptera: Chironomidae). 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 4169 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 256 records from Herpetofauna asociada a ecosistemas de Buenaventura, Valle del Cauca. EPA-IIAP 2019. 3 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 4 records from Re-visiting the Aphidius urticae s. str. group: re-description of Aphidius rubi Starý and A. silvaticus Starý (Hymenoptera: Braconidae: Aphidiinae). 864 records from Caracterizando la diversidad de especies con códigos de barras del ADN en un grupo de avispas parasitoides: un caso de estudio en un área natural protegida mexicana. 125 records from Review of the genus Meganola Dyar, 1898 (Lepidoptera: Nolidae, Nolinae) from Korea, with the description of a new species. 2534 records from Elaboration de table de tarif de cubage multispécifique (I). 1 records from The cumacean genus Iphinoe (Crustacea: Peracarida) from Italian waters and I. daphne n. sp. from the northwestern Adriatic Sea, Mediterranean. 2 records from A new tropical montane firefly genus and species, active during winter and endemic to the southeastern Atlantic Rainforest (Coleoptera: Lampyridae). 18820 records from Cowan Tetrapod Collection - Mammals. 20 records from High diversity and endemism in the genus Cautires Waterhouse, 1879 (Coleoptera: Lycidae) from the Malay mountain forests, with the descriptions of fourteen new species. 1818 records from Actualización de la información sobre los maíces criollos de Oaxaca. 541 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 21 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 97 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 205 records from Bark and Ambrosia Beetles of Vermont from Thomas H. Atkinson. 240 records from Phytoplankton abundance in surface water in May 1996, Pisco, Peru. 740 records from Pollen profile ADR309. 146 records from The genus Sicoderus Vanin 1986 (Coleoptera: Curculionidae: Curculioninae: Erodiscini) in the West Indies. 16 records from Insect Collections of Okomu National Park- Nigeria. 291402 records from ARABEL - Arachnologia Belgica. 133601 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 405 records from Heinersdorfer Sumpfwiese. 71 records from (Table 6) Distribution of benthic foraminifera in Neogene sediments of DSDP Site 90-588_Site in the southwest Pacific. 2872 records from Tableaux de prélèvements communaux. Réseau Ongulés sauvages ONCFS-FNC-FDC. 9 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 1 records from Capnia Shasta, A New Species In The Californica Group From Northwestern California (Plecoptera, Capniidae). 2 records from A new species of Isometopus from Iran (Hemiptera: Heteroptera: Miridae: Isometopinae). 1 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 2707 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 6 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM-IEOMA. 9120 records from ICEL (Land - Invertebrates). 29033 records from UTEP Herpetology (Arctos). 2 records from The genus Lindaspio (Annelida: Polychaeta: Spionidae), and a new species from an oil field off Congo, western Africa. 1643 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 107 records from Revision of the genus Miridiba Reitter, 1902 (Coleoptera, Scarabaeidae, Melolonthinae): genital morphotypes and new taxonomic data. 14914 records from Biological Reference Collections ICM-CSIC. 6 records from First Record of Dericorys albidula Serville, 1838 (Orthoptera: Dericorythidae) in Tunisia and Libya. 1977 records from Données des collections d'algues du MNHN. 18 records from Phytoplankton abundance at station Casma_2003-02-27_2, Casma, Peru. 349123 records from AMNH Herpetology Collections. 13097 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 310 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 6 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 137 records from Lynx 2011 présence Occasionnelle Maille 10km Réseau Loup-Lynx ONCFS. 723 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña noviembre 2008. 368438 records from NOAA AFSC North Pacific Groundfish Observer. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Pandionidae. 8679 records from HSU Wildlife Birds. 14505 records from Biodiversidad mastozoológica del Eje Volcánico Transversal. 14 records from The arctic and alpine bumblebees of the subgenus Alpinobombus revised from integrative assessment of species’ gene coalescents and morphology (Hymenoptera, Apidae, Bombus). 3242 records from Biodiversité marine de l’île de La Réunion. Programme BIOLAVE. 226191 records from Odonata Central. 2 records from Two new species of Aphelochaeta (Annelida: Polychaeta: Cirratulidae) from Korean waters. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 348040 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 16 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 33 records from Description of Coeliccia lephuocdieui sp. nov. from the Central Highlands of Vietnam (Odonata: Zygoptera: Platycnemididae) with notes on its congeners. 43 records from Baltic Sea Basin sediments diversity Raw sequence reads. 10098 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: complementary work sites [2010-2014]. 10 records from A new dwarf crayfish (Decapoda: Cambaridae) from floodplain swamps in central Alabama. 118780 records from Mammalogy Collection - Royal Ontario Museum. 2998 records from La Colección Herpetológica de la Estación de Biología Tropical Los Tuxtlas, Veracruz. 10 records from Revision of Afrotropical species of the Philonthus peripateticus species group (Coleoptera: Staphylinidae: Philonthina). 217796 records from Phytochorologie des départements français. 2 records from Studien zur Systematik und Taxonomie der Gattung Hylaeus F. (4) Hylaeus sinensis sp. n. - Nachweis der montan-disjunkten Verbreitung einer Artengruppe um Hylaeus niger B (Apidae, Colletinae). 2 records from Rivulus kayapo n. sp. (Teleostei: Cyprinodontiformes: Rivulidae): a new killifish from the serra dos Caiapós, upper rio Araguaia basin, Brazil.. 932 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 2 records from Dressed in black. A New Ansonia Stoliczka, 1870 (Lissamphibia: Anura: Bufonidae) from Gunung Murud, Sarawak, East Malaysia (Borneo). 13 records from Contribution to the taxonomic knowledge of Ampharetidae (Annelida) from Antarctica with the description of Amage giacomobovei sp. nov.. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 16 records from CBCGDF CCAfa Volunteer Observation Archive. 35 records from Parascolopsis akatamae, a new species of dwarf monocle bream (Perciformes Nemipteridae) from the Indo-West Pacific, with redescription of closely related species P. eriomma. 43 records from Pelmatellus Amicorum Delgado And Ruiz-Tapiador (Coleoptera: Carabidae), A New Species From The Andean Altiplano Of Peru. 243442 records from Carnet B Lorraine. 32 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 45 records from Nannofossil abundance of Hole 74-526C. 38 records from Targeted analyses of Dehalococcoidetes (phylum Chloroflexi) diversity and community structures in marine subsurface sediments.. 1222 records from Ichneumonidae (Hymenoptera) de la reserva de la biosfera El Cielo, Tamaulipas. 3711 records from Dipterists Forum: Field Week 2015 (Nottinghamshire). 2887 records from Enquête participative "Lichens forestiers d'Auvergne et du Massif Central". 2988 records from Données naturalistes d'Emmanuel SECHET. 324154 records from Seasearch Marine Surveys in England. 17 records from The Afrotropical braconine genus Dioxybracon Granger with descriptions of four new species and new generic synonymy. 25 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 154 records from HRC CRC Small Vessel-Based Monitoring Surveys March-April 2006. 79 records from BIRDRACE Blinde Hühner. 2 records from Two new Opadometa species (Araneae: Tetragnathidae) from Sarawak, Malaysia. 13 records from The discovery of Lepidocyrtoides Schött, 1917 (Collembola, Entomobryidae, Entomobryinae) from the New World, including three new species from Brazil and one from Australia. 5532 records from Riqueza de especies y biodiversidad edáfica de una zona de humedales del Parque Nacional Arrecife de Puerto Morelos, Quintana Roo, México. 4 records from Rhipidocotyle labroidei n. sp. (Digenea: Bucephalidae) from Labroides dimidiatus (Valenciennes) (Labridae). 19 records from Cestode parasites (Neodermata, Platyhelminthes) from Malaysian birds, with description of five new species. 1 records from A new species of bat of the Hipposideros bicolor group (Chiroptera: Hipposideridae) from Central Laos, with evidence of convergent evolution with Sundaic taxa. 210 records from Taxonomy and distribution of African chiggers (Acariformes, Trombiculidae). 14009 records from Collection Trichoptera - SMF. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 4 records from A new species of Sarcofahrtiopsis (Insecta, Diptera, Sarcophagidae) from mangrove forests in the Brazilian Amazon, with a key to species identification. 18315 records from CSIC-Real Jardín Botánico-Colección de Líquenes (MA-Lichen). 1081 records from Soil Invertebrates Surveys from the Chronicle of Nature of the Prioksko-Terrasnyi Biosphere Reserve. 5 records from Pseudonemesia tabiskey, a new species of Pseudonemesia Caporiacco 1955 and new ultramorphological data for the Microstigmatinae (Araneae: Microstigmatidae). 14135 records from Effect of size fractionation and DNA extraction on the diversity and composition of prokaryotic and eukaryotic plankton community. 5 records from Four new species records of Antennoseius and Anystipalpus (Acari: Mesostigmata: Ascidae) phoretic on Carabidae beetles from France. 3652 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 1 records from Description of a new species of Neocordulia Selys, 1882 (Odonata: Libellulidae, Corduliinae) from southern Brazil. 137584 records from Arizona State University Hasbrouck Insect Collection. 4904 records from Mingan Island Cetacean Study 84-07. 3616 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AMPHIBIA. 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 39 records from Integrating data to redescribe Euschistus taurulus Berg (Hemiptera: Pentatomidae). 8 records from A new species of the genus Chrysacris Zheng, 1983 from China (Orthoptera: Acridoidea, Acrididae). 40 records from Taxonomic review of Dendrophryniscus brevipollicatus Jiménez de la Espada, 1870, with revalidation of D. imitator (Miranda-Ribeiro, 1920) and D. lauroi Miranda-Ribeiro, 1926, and description of four new related species (Anura, Bufonidae). 429 records from Collection Strepsiptera SMF. 682 records from University of Amsterdam (NL) - Páramo vegetation research, Talamanca Cordillera, Costa Rica. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 39922 records from Flora of the Korean Peninsula Phase II. 3363 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 146 records from OCEAMM harbor porpoise sightings in the North Sea. 57 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 11 records from BID-AF2015-0004-NAC Collection de Diptères du LEA-UL. 4 records from Two new species of Tardigrada (Eutardigrada: Ramazzottiidae, Macrobiotidae) from the supralittoral zone of the Atlantic Iberian Peninsula rocky shores. 5703 records from MICA - Muskrat occurrences collected by VMM in Flanders, Belgium. 7 records from Occurrence of mammalia relicts at site Dorog. 3784 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 7 records from Two new remarkable genera and two new species of Gyponini (Hemiptera: Cicadellidae: Iassinae) from Brazil. 10217 records from Amphibian specimens of Tochigi Prefectural Museum. 272 records from Nannofossil abundance of Hole 78-542. 12 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 125 records from Inventaire participatif des rhopalocères de Bois-Guillaume, Bihorel et Isneauville. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 3 records from Happywhale - Adelie Penguin in Southern Ocean. 2 records from A new genus, Perplexacara, and new generic placements of species of Australian marsh beetles (Coleoptera: Scirtidae) based on morphology and molecular genetic data. 85774 records from MDFRC macroinvertebrate survey. 1 records from Rhysacephala masneri n. sp. (Xiphydriidae), the first symphytan wasp recorded from Lord Howe Island. 5200 records from R-Bryophyta - Herbário do Museu Nacional - Bryophyta. 6 records from Morphology of the males of seven species of Ortheziidae (Hemiptera: Coccoidea). 128 records from Inventaire des reptiles 2014. 10 records from A New Genus And Species Of Orsillinae (Heteroptera: Lygaeoidea: Lygaeidae) From Argentina. 7 records from Mamíferos de un Área Degradada por Actividad Minera en la Costa Caucana. 133 records from Recolección de frutos para evaluar su potencial de germinación en tres estados de maduración (inmaduro, intermedio y maduro). 2 records from Two new charismatic Pristimantis species (Anura: Craugastoridae) from the tepuis of “ The Lost World ” (Pantepui region, South America). 589 records from Programme ACT : Répartition Pie bavarde 2005 - 2009 Coordonnées GPS Lambert 93. 83 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 29412 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 9 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 3 records from A new species of Coriella, Coriella chernyshevi n. sp. (Entoprocta, Barentsiidae), with comments on the genera Coriella and Pedicellinopsis. 17 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 2969 records from Cladocera distribution updates 2014. 6 records from Two new species of Lauratonema (Nematoda: Lauratonematidae) from the intertidal zone of the East China Sea. 31719 records from Field Museum of Natural History (Geology) Fossil Invertebrates Collection. 95 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 94 records from Revision of the Agrilus purpurifrons species-group (Coleoptera, Buprestidae, Agrilinae). 20228 records from Inventaire de la flore de Charente-Maritime 2017. 6 records from Eulepida mbala, a new species from Zambia (Coleoptera: Scarabaeidae: Melolonthinae). 3 records from Nomenclature and synonymic remarks on two species of Eupterotidae (Lepidoptera) described by Johan Christian Fabricius, and notes on related species. 185 records from Apteronotus caudimaculosus n. sp. (Gymnotiformes: Apteronotidae), a sexually dimorphic black ghost knifefish from the Pantanal, Western Brazil, with a note on the monophyly of the A. albifrons species complex.. 67 records from Evaluación del efecto de esponjas arrecifales en el asentamiento larval de corales escleractinios. 2 records from Studies in Neotropical Pseudophyllinae: A new genus of Cocconotini from the ColombianAndes and new subfamily assignment of the Dominican genus Anacaona (Tettigoniidae: Pseudophyllinae: Cocconotini). 10 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 5 records from Nannofossil abundance of Hole 2-11. 1816 records from Pollen profile from sediment core AV14_K2-3. 122 records from Scottish Beaver Trial incidental species records. 18 records from Bonaire Turtle Tracking 2012 (aggregated per 1-degree cell). 3 records from Neotype designation for Rhinogobius carpenteri Seale 1910, and its placement in Tukugobius Herre 1927 (Teleostei: Gobiidae). 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 4 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 191 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 14 records from (Table 1) Relative abundances of benthic foraminifera in ODP Hole 117-725C. 4446 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 1848 records from Fungi of parks, forests and reserves of New Jersey, 2018. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 39 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 539 records from Phenological Center - Birds (Murmansk). 150 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 61 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 6748 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 5895 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 321 records from Echinoderms from the Seaflower Biosphere Reserve. 5 records from Volutellonectria (Ascomycota, Fungi), a new genus with Volutella anamorphs. 198 records from Programme ACT : Répartition Alouette lulu 1996 - 2000 Coordonnées GPS Lambert 93. 90 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 6 records from Gobiesox lanceolatus, a new species of clingfish (Teleostei: Gobiesocidae) from Los Frailes submarine canyon, Gulf of California, Mexico. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 16 records from Cryptic diversity in the Azorean beetle genus Tarphius Erichson, 1845 (Coleoptera: Zopheridae): An integrative taxonomic approach with description of four new species. 22 records from Redescription of the genus Koumansetta (Teleostei: Gobiidae), with description of a new species from the Red Sea. 1 records from First record of family Dipsocoridae (Hemiptera: Heteroptera: Dipsocoromorpha) from the Korean Peninsula and a new generic combination for Cryptostemma japonicum Miyamoto. 85 records from Nannofossil abundance of Hole 49-408. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 3 records from Analyses of the recent components of sediment core PS1011-1. 45 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/562-1. 69 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 26 records from Schwedische Oribatei (Acari). III.. 1 records from Hypochthonius rufulus. 208 records from Chapter 7: Linnaean Plant Names and their Types (part V). 33 records from MVZ Herp Observations (Arctos). 45 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100260. 243 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 2 records from A new species of Aegidium Arrow (Coleoptera: Scarabaeidae: Orphninae) from Colombia. 2 records from A new species of the subgenus Tachycines (Tachycines) (Othoptera: Rhaphidophoridae) from Guizhou, China. 336 records from Distribution of xylotrophic fungi of the genus Daedaleopsis in the Asian part of Russia from 1978 to 2019. 41280 records from Polymetallic nodule field Targeted loci environmental. 3290 records from Uncultured eukaryotes Targeted Locus (Loci). 4 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 4408 records from (Table 1) Stratigraphic occurrence of selected diatom species from ODP Hole 105-647A. 21808 records from Banksia Atlas. 308 records from (Table 2) Species composition of algae and cyanobacteria encountered in plankton of the Large Aral Sea on June 2-8, 2008. 13 records from Coleção de Coleoptera da Universidade de Brasília. 45 records from Herpetofauna de la expedición Monte y Pinal - Proyecto Boyacá BIO UPTC. 647 records from Twenty-two new species in the genus Hyphantrophaga Townsend (Diptera: Tachinidae) from Area de Conservación Guanacaste, with a key to the species of Mesoamerica. 83 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 1 records from A new delineation for Oreocharis incorporating an additional ten genera of Chinese Gesneriaceae. 96 records from Warnowtal (Rostock). 3 records from MiSeq 16S rRNA gene (archaeal 16S rRNA gene) sequences of 12 SCS sediments. 7 records from A new genus of the mite family Scutacaridae (Acari: Heterostigmata) associated with Trinervitermes trinervoides (Isoptera: Termitidae) from South Africa. 4 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 39 records from A review of all Recent species in the genus Novocrania (Craniata, Brachiopoda). 1 records from Celaeno coccinea. 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 265696 records from Compost microbe establishment and growth in agricultural soils. 69 records from Bostryx tortoranus (Doering, 1879) species complex (Gastropoda: Stylommatophora: Bulimulidae), a review of taxonomy and distribution of endemic species from Argentina. 189673 records from National Benthic Inventory. 13 records from Nannofossil abundance of Hole 6-48B. 173311 records from Marine benthic dataset (version 1) commissioned by UKOOA. 13 records from An annotated species list of regular echinoids from Sri Lanka with notes on some rarely seen temnopleurids. 14502 records from Propuesta de actualización del Catálogo de Autoridades Taxonómicas (CAT) de Lepidoptera: Heterócera para la Península de Yucatán. 29876 records from European Moth Nights. 7 records from New Species of Blindsnakes (Squamata: Gerrhopilidae) from the offshore islands of Papua New Guinea. 172 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 577 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 3300 records from Benham Rise 16S raw sequence reads. 6762 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from New species of Heteropathes (Anthozoa: Antipatharia) expands genus distribution to the NE Atlantic. 2 records from A new addition to the subfamily Anabropsinae (Orthoptera: Anostostomatidae) from China. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 1111 records from 16S rDNA metagenomes of Western Balkans glacial lakes sediments. 13 records from New species of Tingidae (Insecta: Heteroptera) from Madagascar. 1017 records from BUND - Dassower See (Lübeck/Dassow). 58758 records from Données naturalistes de Monsieur François FOURNIER. 443 records from Nannofossil abundance of Hole 29-277. 444 records from Phenology of Crocus. 997 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 21 records from Revision of the genus Setosella (Bryozoa: Cheilostomata) with description of new species from deep-waters and submarine caves of the Mediterranean Sea. 1727 records from TWIC Record a Raptor Survey. 958 records from Epifitas del piedemonte de Yopal. 18 records from Redescription of two species of wobbegongs (Chondrichthyes: Orectolobidae) with elevation of Orectolobus halei Whitley 1940 to species level.. 54188 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 4 records from Sächsische Schweiz (Wehlener Gebiet). 5 records from Coarazuphium lundi (Carabidae: Zuphiini), a new Brazilian troglobitic beetle with the designation of a neotype for C. pains Álvares & Ferreira, 2002. 15 records from Three new species of the genus Rhyzobius Stephens, 1829 from New Guinea (Coleoptera: Coccinellidae: Coccidulini). 22 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 7895 records from Bryophytes specimens of Akita Prefectural Museum. 32 records from Molecular study supports the position of the New Zealand endemic genus Lamellomorpha in the family Vulcanellidae (Porifera, Demospongiae, Tetractinellida), with the description of three new species. 29 records from Ours 2004 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 343 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 8 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 30 records from Revisión del género Microogenius Gutiérrez (Coleoptera: Scarabaeidae: Rutelinae: Rutelini), con descripción de dos nuevas especies altoandinas. 2624 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 701 records from Données naturalistes de Monsieur JOURDE Rémi. 124 records from Wiesenbiotop am Wasserturm. 1 records from A new Atheta species from the West Caucasus and a redescription of A. brevapicalis (Coleoptera: Staphylinidae: Aleocharinae). 873 records from Programme ACT : Répartition Geai des chênes 2008 - 2012 Coordonnées GPS Lambert 93. 20 records from A new species of sardine, Sardinella electra (Teleostei: Clupeiformes: Clupeidae), from the Ryukyu Islands, Japan. 1385 records from Regeneración, crecimiento y dinámica poblacional del pino azul Pinus maximartinezii Rzedowski. 17350 records from CAS Entomology Type (TYPE). 19 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 7 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 31 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 5 records from Five new species of the genus Primulina (Gesneriaceae) from Limestone Areas of Guangxi Zhuangzu Autonomous Region, China. 354 records from Sponges of the Guyana Shelf. 3 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 119 records from Kinorhyncha. 12194 records from MBML-Anfibios - Coleção de Anfíbios MBML. 2984 records from North East Scotland Amphibians & Reptiles 1850 - 2016. 2423 records from Base de datos de la Colección zoológica del Instituto de Investigación de zonas desérticas de la Universidad Autónoma de San Luis Potosí (BDCZIID-UASLP). 599 records from Marine subseafloor sediment Targeted Locus (Loci). 19 records from Mycomystes nigriventris sp. nov. (Coleoptera: Erotylidae: Tritomini) from South America, with insights into the genus Mycomystes Gorham. 2 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 7 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 140 records from The Oncometopia orbona species group (Hemiptera, Cicadellidae, Proconiini). 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 11 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 43652 records from Nutrient addition mesocosm experiment Targeted Locus (Loci). 134 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 7054 records from RNF - Données de l'Association GEREPI (GEstion de la REserve naturelle nationale du PInail). 8963 records from SuLaMa bird occurence data. 50 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 1 records from Description of a new species of Acrostichus Rahm 1928 (Nematoda: Diplogastridae) from India with a note on its position and relationship with the congeners. 1 records from A new genus of giant lacewing (Insecta, Neuroptera, Ithonidae) from the Middle Jurassic of China. 3 records from New data of Nazeris Fauvel in Xizang, China (Coleoptera, Staphylinidae, Paederinae). 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 26 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 31 records from Bulletin d'informations de l'Association française de Lichénologie. 24 records from Nannofossil abundance of Hole 10-89. 57 records from Ostracoda abundance of Hole 42-372. 15 records from New genus and species of Leptopsaltriini (Hemiptera: Cicadidae: Cicadinae) from China and Vietnam, with colour-changing behaviour reported for the first time in Cicadoidea. 75 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 48 records from Nannofossil abundance of Hole 30-285A. 157 records from A Revision of the Nearctic Predaceous Midges in the Bezzia (Bezzia) pulverea complex (Diptera: Ceratopogonidae). 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 3600 records from Amphibian and reptile records for Great Britain 2016-2019. 1 records from VANILLA RIVASII (ORCHIDACEAE), A NEW SPECIES FROM THE COLOMBIAN PACIFIC REGION. 170 records from The taxonomic history of Indo-Papuan groundsnakes, genus Stegonotus Duméril et al., 1854 (Colubridae), with some taxonomic revisions and the designation of a neotype for S. parvus (Meyer, 1874). 12 records from On the land snail Rhagada Albers, 1860 (Gastropoda: Camaenidae) from across the Lesser Sunda Islands. 356 records from Morphologische Daten von Puffinus creatopus. 272 records from El rorcual común Balaenoptera physalus, en el Golfo de California, México. 5 records from Three Oriental species of Pseudoaerumnosa Rudzinski (Diptera, Sciaridae) from China. 8 records from Three new species of the Stenus cephalotes group fom Zhejiang, East China (Coleoptera, Staphylinidae). 23456 records from WTSWW Data: All Taxa (West Wales). 1494 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 12 records from (Table 2) Ostracode distribution in ODP Hole 122-760B. 19 records from Census of the fruit and flower chafers (Coleoptera, Scarabaeidae, Cetoniinae) of the Macau SAR, China. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 123 records from Regionalpark(Hattersheim). 124 records from New species and records of Caulleriella (Annelida, Cirratulidae) from shelf and slope depths of the Western North Atlantic Ocean. 26 records from A new species of Phrynus Lamarck, 1801 (Arachnida: Amblypygi), from Trinidad and Tobago, and Venezuela, with a redescription of Phrynus pulchripes (Pocock, 1894). 148 records from Herbarium BSG Hepaticopsida. 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 20 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 1 records from Description of the last stadium larva of Erythrodiplax abjecta (Anisoptera: Libellulidae) from the eastern Colombian Andes. 811 records from Revision of the Neotropical caddisfly genus Phylloicus (Trichoptera: Calamoceratidae). 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 24 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 72 records from A New Mormoopid Bat From The Oligocene (Whitneyan And Early Arikareean) Of Florida, And Phylogenetic Relationships Of The Major Clades Of Mormoopidae (Mammalia: Chiroptera). 68 records from Unter hellen Zinnen und finsteren Grotten. 9 records from New data on the genus Syndicus Motschulsky (Coleoptera: Staphylinidae: Scydmaeninae) from Yunnan, southern China. 81214 records from Museu Paraense Emílio Goeldi - Ornithology Collection - Feathers_and_Skin. 10246 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 7 records from Happywhale - Northern Right Whale Dolphin in North Pacific Ocean. 271 records from Fossil (NSMK-FO). 5 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 47 records from Genus Stathmopoda Herrich-Schäffer, 1853 (Lepidoptera: Stathmopodidae) from China: Descriptions of thirteen new species. 3 records from Two new species of the genus Odochilus Harold, 1877 (Coleoptera: Scarabaeidae Aphodiinae: Odochilini). 16 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 22 records from Ahuyentamiento, rescate y reubicación de fauna en el área de influencia directa del proyecto Hidroeléctrico Mulatos II. 6648 records from Inventory of plant species through Benin (West Africa). 8 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 6 records from The bee genus Caenaugochlora (Hymenoptera, Apoidea) and its constituent subgenera, with new species of Caenaugochlora s. str. from Ecuador. 3921 records from South Caribbean Diversity. 25 records from Vom Wert alter Amateursammlungen - vier Spinnenarten neu für die Schweiz in der Sammlung Ketterer. 466 records from Northern elephant seals post-molting 2018 (aggregated per 1-degree cell). 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 158 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 4853 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 6 records from Neoplecostomus canastra, a new catfish (Teleostei: Siluriformes) species from upper Rio Paraná basin. 411 records from SuLaMa reptile survey I 2012. 61 records from Shrews of Poland. 620 records from Museum TwentseWelle (NL) - Fossil Sponges Collection. 106 records from Marine Plants (NHMC-SA). 4377 records from Microbial populations of Lascauxs Apse in relation to collembola and black stains on cave walls.. 2 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica). 486 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 3 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 873 records from Programme ACT : Répartition Grive musicienne 2006 - 2010 Coordonnées GPS Lambert 93. 4 records from A new species of Ephoron Williamson, 1802 (Ephemeroptera: Polymitarcyidae) from Thailand. 9 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 22 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 35 records from Two new trans-Andean species of Imparfinis Eigenmann & Norris, 1900 (Siluriformes: Heptapteridae) from Colombia. 5 records from A new species of the Neotropical genus Beebeomyia (Diptera: Richardiidae) with observations of its biology on Dieffenbachia oerstedii (Araceae). 1819 records from UNCW Right Whale Aerial Surveys 2008. 58 records from Nouveautés dans le genre Lomariopsis Fée (Pteridophyta, Lomariopsidaceae) à Madagascar: trois espèces nouvelles et une espèce africaine nouvellement signalée. 1524 records from Pollen record of sediment core Bokanjacko Blato 1. 21 records from Cape Verde (Cabo Verde) 2005: Loggerhead Turtles (aggregated per 1-degree cell). 1 records from Description of Gondwanoscurus curleri sp. nov. from the West Usambara Mts, Tanzania (Diptera: Psychodidae). 26 records from New acoustic and molecular data shed light on the poorly known Amazonian frog Adenomera simonstuarti (Leptodactylidae): implications for distribution and conservation. 1 records from Oribates fusifer. 4 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 2 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 7 records from A new species of Catomus Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from the Aeolian archipelago (Sicily, Italy). 1518 records from Mammals in the collection of Zoological Museum of NSNHM (the National Science and Natural History Museum at the National Academy of Sciences of Ukraine, Kyiv): Erinaceidae, Talpidae, Soricidae, Myoxidae, Sminthidae. 27 records from Nemertini - SMF. 5 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 2 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 3 records from A new species of frog (genus Eleutherodactylus) from a cloud forest in Western Colombia. 1285 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 922 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 128182 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 4 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 3 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 23 records from Happywhale - Crabeater Seal in Southern Ocean. 1639 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 209 records from A review of the genus Hexachaetoniella Paschoal in Australia (Acarina: Cryptostigmata: Pedrocortesellidae). 79263 records from Marine Offshore Seabed Survey data held by JNCC. 99 records from Nanoplankton abundance at station GeoB2006-4. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 313 records from Données naturalistes de Monsieur LEFEBVRE François. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 439379 records from Herbarium of Taiwan Forestry Research Institute. 37 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 22 records from Ackerrain Plönhagen. 1004 records from Données odonates. 258 records from Malawi-Histeridae-Biodiversity-Data. 29 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 3 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 7 records from Further Descriptions Of Western North American Podmosta Larvae And Their Separation From Ostrocerca Larvae (Plecoptera: Nemouridae). 12 records from Rotundocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae). 1 records from Oribates calcaratus. 297213 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 18 records from Happywhale - Short-finned Pilot Whale in North Atlantic Ocean. 38 records from A new species of the genus Tetragonopterus Cuvier, 1816 (Ostariophysi: Characiformes: Characidae) from the rio Tocantins drainage, Brazil. 6412 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 4644 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 4046 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 62 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 14 records from Four new species of Mileewini leafhoppers (Hemiptera: Cicadellidae: Mileewinae) from China, with a checklist to Chinese species. 272 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 78 records from Banco de Semillas de Boyacá. 2217 records from Données naturalistes d'Anaïs MAS. 1487 records from Microbial community diversity in Arctic marine sediments and Planktonic microbial. 111 records from Palynological analysis of sediment core GeoB9508-5. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 63 records from Novel taxa of Cheilostomata Bryozoa discovered in the historical backlogs of the Iziko South African Museum. 9795 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 65 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 52 records from Pelvicachromis signatus and Pelvicachromis rubrolabiatus, two new cichlid species (Teleostei, Perciformes) from Guinea, West Africa.. 4 records from Abundance of benthos infauna at station GIK23065-1. 305 records from uncultured eukaryote Raw sequence reads. 29137 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 41 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 167 records from Flux data of NU2_trap (Table A1). 11 records from Revision of the bee genus Chlerogella (Hymenoptera, Halictidae), Part I: Central American species. 2844793 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 228 records from Bishop's University Insect Collection (BUIC). 18 records from ALTERECO_2017_12_18. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 16 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 3387 records from Sediment metagenome. 15180 records from Anymals+plants - Citizen Science Data. 1538 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 21 records from Happywhale - Blue Whale in Southern Ocean. 10105 records from Happywhale - Humpback Whale in North Atlantic Ocean. 3139 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 77333 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 1824 records from CNAN/Scorpiones. 104 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 4 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 4 records from Two new genera and species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae) and redescription of the type species of Paraidioscopus. 7 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 7 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 14 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 7 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 19665 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 412 records from Collection de C.C.H. Jongkind aux Monts Nimba. 5 records from A new Brazilian species of Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorinae), a predator of Tinocallis kahawaluokalani (Kirkaldy) (Hemiptera, Aphididae). 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 4 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 817 records from Programme ACT : Répartition Tourterelle turque 1997 - 2001 Coordonnées GPS Lambert 93. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 243 records from Thistles species and abundance. 3 records from Impatiens wutaishanensis (Balsaminaceae), a new species from Southeast Yunnan, China. 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 264 records from Checklist of decapod crustaceans from the coast of the São Paulo state (Brazil) supported by integrative molecular and morphological data: IV. Infraorder Anomura: Superfamilies Chirostyloidea, Galatheoidea, Hippoidea and Paguroidea. 751 records from Programme ACT : Répartition Pie bavarde 2007 - 2011 Coordonnées GPS Lambert 93. 13 records from Notes on types of Australian Chartocerus Motschulsky (Hymenoptera: Signiphoridae). 10738 records from The Suguru Igarashi Insect Collection (Lepidoptera: Lycaenidae) of The University Museum, The University of Tokyo. 86685 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 14 records from MfN - Fossil invertebrates IIa. 2 records from Hawksbill turtle - Milman Island (aggregated per 1-degree cell). 4 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 106 records from sediment microorganism Metagenome. 12548 records from herbarium_database. 50 records from Pteridofitas 1er Trimestre 2021 B. 221 records from Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae Anthophagini) of the Iberian Peninsula. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 228 records from Gomex Sperm Whale Survey 2000. 78 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 6366 records from Modernisation des ZNIEFF du PnrL. 36 records from The West and Central African species of Vepris Comm. ex A. Juss. (Rutaceae) with simple or unifoliolate leaves, including two new combinations. 38 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 5 records from Dombeya sevathianii (Malvaceae): A new critically endangered species endemic to Mauritius (Indian Ocean). 1201 records from Monocotyledonous Geophytes of Fergana Valley. 596 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 10 records from Occurrence of mammalia relicts at site Niederlehme. 1264 records from Grand Voyeux - Suivis scientifiques. 46 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 179 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 86 records from UWIZM Cnidarians. 78 records from Nannofossil abundance of Hole 9-84. 798 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Planothidium galaicum sp. nov. (Bacillariophyta, Achnanthidiaceae), a new diatom species from Galician coast, Spain. 356 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 150 records from Ningaloo Outlook Whale Shark tracking (aggregated per 1-degree cell). 11 records from New records and a new species of bivalve (Mollusca: Bivalvia) from Miocene hydrocarbon seep deposits, North Island, New Zealand. 280 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 38175 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 176082 records from Tasmanian Museum and Art Gallery provider for OZCAM. 965 records from TTRS Mammals. 41 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 936 records from Mushroom (KIDR-MR). 15 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 3286 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 1632 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 242 records from Colección Ornitológica del Museo de Historia Natural de la Universidad de la Amazonia. 45 records from Brown bear monitoring data from Deosai National Park. 624 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 1857 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 99380 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 916 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 1 records from Occurrence of mammalia relicts at site High Furlong. 2869 records from University of Sindh Jamshoro Herbarium. 215 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 2741 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT Tromsø Museum. 30 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 48 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 1 records from A new species of freshwater Chaetonotidae (Gastrotricha, Chaetonotida) from Obodska Cave (Montenegro) based on morphological and molecular characters. 24 records from Faunal assemblage of sediment core TR149-32. 787 records from Programme ACT : Répartition Pie bavarde 2009 - 2013 Coordonnées GPS Lambert 93. 76 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 54 records from A new genus and species of pigeon (Aves, Columbidae) from the Kingdom of Tonga, with an evaluation of hindlimb osteology of columbids from Oceania. 4 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 3 records from Two new scale insect species (Hemiptera: Coccomorpha: Acanthococcidae and Pseudococcidae) and a new country record from protected areas in Iran. 1 records from Hoplophora ardua. 31 records from New Descriptions Of North American Taenionema Larvae (Plecoptera: Taeniopterygidae). 1 records from Memecylon pseudomegacarpum M. Hughes (Melastomataceae), a new species of tree from Peninsular Malaysia. 111 records from Birdrace-Uhulogen-Lippe. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 1640 records from La familia Asclepiadaceae en México. 18 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 11 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 83 records from Birdrace-Die_Vogelscheuchen-Herford. 373 records from Otter survey of Ireland 2004 & 2005. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 20 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 1308 records from Happywhale - Gray Whale in North Pacific Ocean. 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 129891 records from Suivi Temporel des Rhopalocères de France (STERF). 43 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 1289 records from Fossil specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 940 records from SeaTurtle surveys on Braamspunt by Green Heritage Fund of Suriname. 54 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 49 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 51 records from Bryophyte speciments of Toyota City Nature Sanctuari (TCNS).. 61 records from Alien Species in Poland - Plants. 401 records from Données de VINCENT Alexis (SAPROX). 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 2 records from A new species of Symbiopsocus Li (Psocodea: “ Psocoptera ”: Psocidae) from Taiwan, China, with a revised checklist and key to species. 50 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 51 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 82 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 314 records from Nannofossil abundance of Hole 66-490. 130 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 2901 records from Fossil Specimens of Komatsu City Museum. 37 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 9 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 773 records from Nannofossil abundance of Hole 82-558A. 446 records from Programme ACT : Répartition Etourneau sansonnet 2006 - 2010 Coordonnées GPS Lambert 93. 3209 records from BioGIS - Mammals - SPNI. 503 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 5 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 151 records from CHAS Botany Collection (Arctos). 237 records from Avifauna asociada a humedales urbanos del municipio de Quibdó - Chocó, 2019. 4 records from Leuctra Pinhoti, A New Species Of Stonefly (Plecoptera: Leuctridae) From Alabama, U. S. A.. 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 119 records from Naturschutzgebiet Lochbusch-Königswiesen. 4 records from Bryoerythrophyllum subcaespitosum (Pottiaceae), a new combination for a neglected species from South America. 70 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 15 records from Oxynoemacheilus phasicus, a new nemacheilid loach from the eastern Black Sea basin with some remarks on other Caucasian Oxynoemacheilus (Teleostei: Nemacheilidae). 7814 records from Odonata de Veracruz. 622 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 20 records from Happywhale - Sei Whale in South Pacific Ocean. 6689 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 3 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 15 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 35 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 2 records from Charletonia Talebii N. Sp. From Iran (Acari, Prostigmata, Erythraeidae). 4 records from Tortonian teleost otoliths from northern Italy: taxonomic synthesis and stratigraphic significance. 4 records from A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera Cicadellidae: Eurymelinae). 11 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 255 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 10301 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 77 records from A survey of small mammals in the Volta Region of Ghana with comments on zoogeography and conservation. 16332 records from Database for alien invasive plants occurrences in Germany. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 74 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 353 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 8999 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 2 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 407 records from Strathclyde badger sett surveys 1996-2000. 71 records from UNCW JAX Aerial Survey -Left side- 2017. 8 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 9856 records from Spider (NSMK-SP). 30943 records from OUPR - Herbário "Professor José Badini". 8 records from Nannofossil abundance of Hole 58-442B. 64 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 100 records from Registros de Palma de cera palma (Ceroxylon quindiuense) por medio de fotografías aéreas en el parque Chingaza. 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 101 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 12404 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 42 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 1 records from Resurrection of the earthworm species Dendrobaena fedtschenkoi (Michaelsen, 1900), a former synonym of Dendrobaena byblica (Rosa, 1893) (Clitellata: Megadrili). 23 records from Taxonomic review of Coccobius species (Hymenoptera: Aphelinidae) from China, with notes on their use in biological control of scale insect pests (Hemiptera: Diaspididae), and description of a new species. 90 records from Nottekanal, Klasse 7 - 10. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 5918 records from Australian Coral Ecoregions. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 4733 records from Inventaire des Mollusques Sphaeriidae de France. 1 records from The fossil crown wasp Electrostephanus petiolatus Brues in Baltic Amber (Hymenoptera, Stephanidae): designation of a neotype, revised classification, and a key to amber Stephanidae. 17073 records from données aranéologiques de CORNIC Jean-François. 742 records from Programme ACT : Répartition Alouette des champs 2000 - 2004 Coordonnées GPS Lambert 93. 477 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 12 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 3 records from A new species of the genus Sovia Evans, 1949 from South Central Yunnan, China (Lepidoptera, Hesperiidae). 882 records from Sea shells of New South Wales. 9 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 4222 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 972 records from NEFSC North Atlantic Marine Mammal and Turtle Aerial Abundance Survey 2007. 1 records from Filogeografia mitocondrial y nuclear de la Tangara rosada Rhodinocichla rosea (Lesson, 1832): el efecto del aislamiento geográfico y el nicho ecológico en los procesos de divergencia evolutiva.. 50 records from Flora und Fauna im Brexbachtal. 5 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 6910 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 146 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 6099 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 2 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 387 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 72170 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 132 records from Pollen profile II/B at Krumbach, Germany. 22136 records from Weevil and Bark Beetle records via iRecord. 22 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 8 records from A new apterous rove beetle genus (Coleoptera: Staphylinidae) from the Northern Andes with an assessment of its phylogenetic position. 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 1 records from Nannofossil abundance of Hole 4-26A. 43 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 13303 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 77 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 440 records from Wichita State University Collection. 86 records from Données naturalistes de Pierre-Alexis RAULT. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 4739 records from Dark ocean microbial diversity. 846 records from Taxa occurrences and composition of benthic macroinvertebrates from biodiversity surveys on Lake Victoria, Uganda (2001-2006). 14 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 21 records from Taxonomic review of the genus Assamacris (Orthoptera: Acrididae: Catantopinae) with a new species and a newly discovered female. 647 records from pbzt_insect_biodiversity. 7 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 281 records from NZCS Upper Tapanahony Expedition 1991. 34 records from A taxonomic revision of Otomantis Bolivar, 1890 (Mantodea: Hymenopodidae, Acromantinae) with description of five new species. 1 records from Oppia nitens. 307 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 24 records from Tanzanian Vertebrate Collection. 2 records from DD_cyano Targeted loci environmental. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 68 records from MIRC NAVFAC Incidental Sightings - Vessel 1965-2014. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 32 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 13518 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 4 records from Description of a new species of Andaeschna (Odonata: Aeshnidae) from the Western Colombian Andes. 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 1313 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 154 records from Eusocial wasp fauna of Sulawesi Island, the central island of Wallacea (Hymenoptera: Vespidae; Polistinae, Vespinae). 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 111 records from University of Algarve and ICNB Cetacean Sightings 1999. 3 records from A new flower bug of the genus Montandoniola (Hemiptera: Heteroptera: Anthocoridae), a predator of gall-forming thrips on black pepper in southern India. 2 records from Contributions to the palaeofauna of Ptinidae (Coleptera) known from Baltic amber. 229 records from Earthworms of mole burrows in the forest zone of Western Siberia. 173415 records from Hymenoptera specimen database of Kyushu University. 3 records from Lemyra persephone, a new autumnal species from Yunnan, southwestern China (Lepidoptera, Erebidae, Arctiinae). 3250 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 17 records from Records and redescription of a mygalomorph spider genus ignored for over 100 years with a new species: the genus Atmetochilus Simon, 1887 (Araneae Nemesiidae) in Thailand. 771649 records from Finnish Floristic Database (Literature Sources). 174 records from The Myriapoda Collection of the National Museum of Nature and Science. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 72185 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 633 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 7 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 232 records from Inventaire avifaune. 30291997 records from iNaturalist Research-grade Observations. 277 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 1 records from Lysimachia rupestris F. H. Chen & C. M. Hu (Primulaceae): a new record for the flora of Vietnam and reconsideration of its taxonomical position. 100 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 3 records from А new species of Alona Baird, 1843 (Cladocera: Chydoridae) from the ancient Lake Ohrid. 37 records from Bohemannia auriciliella (Nepticulidae) specimen data. 78 records from A contribution to the knowledge of the prominent moths (Lepidoptera, Noctuoidea Notodontidae) of the Maputo Special Reserve with descriptions of four new species. 29 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 64 records from Lynx 1996 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 45 records from Nannofossil abundance of Hole 39-359. 4159 records from DBG Mirabilis rotundifolia Demographic Monitoring. 80 records from An updated checklist of Iranian Encyrtidae (Hymenoptera, Chalcidoidea). 71 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 217 records from Inventaire des odonates 2014. 94 records from Nannofossil abundance of Hole 49-412. 16 records from Genética de la Conservación del Oso Andino en el Parque Nacional Natural Cordillera de los Picachos y área de amortiguación. 21 records from Abundance of benthos infauna at station PS1240-1. 1015 records from Marine algal flora of Flores and Corvo Islands, Azores. 6 records from New records of biting midges (Diptera: Ceratopogonidae) from the United Arab Emirates, with a description of a new species. 1079 records from Mediterranean seabird surveys 99/00/02. 4 records from A new species of Lamprodila (Ovalisia Kerremans, 1900) (Coleoptera: Buprestidae) from Sulawesi, Indonesia. 8 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 611 records from Données du Râle gris sur le territoire de la Guadeloupe. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 35 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 1095 records from Amphibian specimens of Kanagawa Prefectural Museum of Natural History. 694 records from données arachnologiques de CARR David. 19 records from Fishes from the Auckland and Campbell Islands, Cape Expedition, 1942-1944. 3 records from Nannofossil abundance of Hole 3-22. 18 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 20 records from Nine new Trechisibus species from Peru and Argentina (Coleoptera: Carabidae: Trechinae). 945 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 7 records from Description of Coeliccia natgeo sp. nov. from Central Vietnam with keys to the males and females of the hayashii-group (Odonata: Zygoptera: Platycnemididae). 36 records from Review of Chinese species of the Oxylipeurus - complex (Phthiraptera: Philopteridae), with descriptions of two new genera and five new species. 61797 records from Fiocruz/CMN - Coleção de Mosquitos Neotropicais. 133 records from BIRDRACE Griffin Wood Warblers. 156 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 2 records from Porifera ZMK. 91 records from Marybio Foundation marine mammal aerial sightings in Bahia San Antonio, Patagonia 2008-2010. 4 records from Two new species of the genus Sinopodisma (Orthoptera: Acridoidea: Catantopidae: Podisminae) from China. 4 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 10 records from New records of the water mite genus Arrenurus Dugès, 1834 from South America (Acari: Hydrachnidia: Arrenuridae), with the description of five new species and one new subspecies. 34 records from Range table from benthic foraminifers in ODP Hole 154-929A. 29 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 56 records from Revision of the genus Tmesiphorus LeConte, 1849 (Coleoptera: Staphylinidae: Pselaphinae) from Japan. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 24442 records from JCT AVH data. 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 26476 records from Heterogeneity of methane seep microbiomes in the NE Pacific. 317 records from Sequences obtained from two sponge genera (Hyrtios, Aiolochroia), one zoanthid (Palythoa), and marine sediments. Metagenome. 265 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 2 records from Bioacoustics review of Anatolian species of the predatory bush-cricket genus Saga (Orthoptera: Tettigoniidae: Saginae) with the description of a new species. 31 records from Exceptional diversity of Tischeriidae (Lepidoptera) from a single tropical forest site in Belize, Central America. 3224 records from Amphibiens de Guyane. 91 records from Nannofossil abundance of Hole 7-62A. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 104862 records from Fish (NSMK-PI). 10 records from Nannofossil abundance of Hole 9-82. 11 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 483 records from Nannofossil abundance of Hole 75-530A. 43 records from Happywhale - Fin Whale in South Atlantic Ocean. 3 records from One new species and new record of the leafhopper genus Watara Dworakowska from Thailand (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini). 10 records from Collection Myriapoda - SNSD. 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 78453 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 78 records from Notes on the subspecies of Plagionotus arcuatus (Linnaeus, 1758) with description of a new subspecies from Iran (Coleoptera: Cerambycidae). 21 records from Revision der Gattung Agachila D & G - M, 1954 (Hemiptera: Heteroptera: Tingidae). 271 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 55 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 3546 records from Dorset SW Pilot species dataset. 87 records from Contrasting species diversification of Eutarsopolipus (Acariformes: Podapolipidae) on Castelnaudia and Notonomus (Coleoptera: Carabidae). 1705 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 3 records from Benthic macrofauna abundance of sediment core 13077-087. 910 records from Alien plants of Salavat. 1 records from On two italian Lithobius species described by Silvestri with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda Lithobiidae). 8 records from Unraveling the species diversity and relationships in the Leptodactylus mystaceus complex (Anura: Leptodactylidae), with the description of three new Brazilian species. 3 records from Review of the Stenoscelidea complex and key to the known genera of Stenoscelideini (Hemiptera: Heteroptera: Coreidae). 5 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 35 records from Inventaire et suivi de la faune écrasée. 78 records from Geographical and bathymetric distribution of mysids (Crustacea: Mysida) in the seas of the Iberian Peninsula. 1000 records from nsmk_mm_2019. 50 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 43 records from A revision of the systematics and distribution of the damselfly genus Prodasineura Cowley, 1934 (Odonata: Zygoptera: Platycnemididae) in Vietnam with description of two new species. 43 records from Vogelstimmenführung durch den Tiergarten. 384 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 11 records from The first blind spirostreptid millipede, found in a cave in Morocco; with notes on the genus Odontostreptus Attems, 1914 (Diplopoda, Spirostreptida, Spirostreptidae). 4 records from A new species and comparative morphology of Philippine sea biscuits (Echinoidea Clypeaster). 2923 records from Tetrápodos de Uruguay. 109 records from Database of Arctic lamprey (Lethenteron camtschaticum (Tilesius, 1811)) occurrences in Russia and actual samples deposited in the A.N. Severtsov Institute of Ecology and Evolution.. 4 records from Craspedotropis gretathunbergae, a new species of Cyclophoridae (Gastropoda: Caenogastropoda), discovered and described on a field course to Kuala Belalong rainforest, Brunei. 2 records from Phylogenetic analysis and systematic position of two new species of the ant genus Crematogaster (Hymenoptera, Formicidae) from Southeast Asia. 194 records from Données de la naturaliste Giordano Charlotte provenant de la base de donnée du SINP Île-de-France CETTIA. 7994 records from Phenology and biological traits of adult migrating atlantic salmon (Salmo salar) sampled by trapping in the survey in the Nivelle river (France). 9 records from Diatom abundance of Hole 60-460. 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 39903 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 7604 records from Lepidoptera of Mordovia State Nature Reserve. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 8 records from A new species of freshwater crab of the genus Badistemon Yeo & Ng, 2007 (Decapoda: Brachyura: Potamidae: Potamiscinae) from Manipur State, India with the reassignment of Potamiscus pealianus (Wood-mason, 1871). 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 30369 records from MfN - Fossil vertebrates IV. 4 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 49 records from DECAF - AUTEC Sperm Whales - Multiple Sensors - Samples. 3436 records from MEXU/Flora de Oaxaca. 51472 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 2 records from The Genus Episynlestes Kennedy (Odonata: Synlestidae). 6362 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 480 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 188 records from Nannofossil abundance of Hole 66-488. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 3319 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 59 records from Crickets of the subfamily Itarinae Shiraki, 1930 (Orthoptera: Gryllidae) from China with description of a new species and distribution and critical notes on other species. 12040 records from Echinoderm collection of National Museum of Nature and Science. 57 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 7 records from Two new species of Eumeninae from Iran (Hymenoptera: Vespidae). 2923 records from Données naturalistes d'Alain BERLY. 108902 records from Herps Specimens. 38994 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 368 records from Ring ouzel national sample survey in the UK in 1999. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 191 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 6 records from A new fossil species of Trentepohlia (Diptera, Limoniidae) from the Dominican Miocene. 250 records from Inventaire et regroupement de données Natura 2000. 4 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 12996 records from LPO_PACA_2017_12_18. 7 records from Nannofossil abundance of Hole 39-353A. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 227989 records from Oklahoma Vascular Plants Database Provider. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 42 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 48 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 10894 records from Census of species recorded during phytosociological surveys in Benin. 724 records from Programme ACT : Répartition Faisan commun 2009 - 2013 Coordonnées GPS Lambert 93. 6240 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 2 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 1788 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 614 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 32912 records from Collection Pisces SMF. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 1989 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 41458 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 78157 records from Microbial biogeography of 925 geothermal springs in New Zealand. 8 records from NMML Harbor Porpoise Aerial Survey, Cook Inlet, 1991. 4 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 1354 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 27 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 238 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 1553 records from University of Valencia cetacean surveys in the Spanish Mediterranean 2000-2003. 3 records from Oratosquilla septemdentata n. sp. (Crustacea: Stomatopoda: Squillidae), a new species of deep water stomatopod from Halmahera, Indonesia. 4 records from One new species of the genus Xizicus Gorochov, 1993 (Orthoptera: Tettigoniidae Meconematinae) from Guangxi, China. 14567 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 16 records from The endless search for type specimens; illustrations of eleven spider (Araneae Mygalomorphae) species described by Eugène Simon. 7 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 1377 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 325456 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 12 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 5 records from Genome sequencing reveals extraordinary cephalic horns in the Madagascan dung beetle genus Helictopleurus (Coleoptera, Scarabaeinae): insight from a revision of fungicola species group. 44737 records from Botanical Museum, Copenhagen, Mycology Herbarium. 7 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 17840 records from NCSM Mammalogy Collection. 100 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 398 records from Nivå Bay species list, Zealand, Denmark. 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 164 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 91 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 96265 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 9 records from New Vietnamese Species Of The Genus Flavoperla Chu (Plecoptera: Perlidae). 181610 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 14 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 18 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 6 records from Mammalia (JNHM-MM). 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 19059 records from The Vascular Plants Collection of the University of Goettingen. 28334 records from Occurrences de vecteurs de maladies recensées à l'Hôpital de Mènontin. 2084 records from Flora vascular acuática de la cuenca del Río Tamesí. 1 records from Larval morphology of Plagiosterna adamsii (Baly) and P. aenea (Linnaeus) with resurrection of Gastrolinoides Chûjô & Kimoto and P. formosana (Bates) (Coleoptera: Chrysomelidae: Chrysomelinae). 5 records from Two new nematode species of the genus Tobrilus Andrássy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 9 records from New data on brown lacewing genus Wesmaelius Krüger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 82 records from Type locality records of Polycystididae species in the world. 200093 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 5324 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 1122 records from Données naturalistes de Stéphane ORIO. 665 records from Collection Echinodermata - ZMB. 442 records from Inventario herpetofaunístico del noroeste de Hidalgo. 32216 records from EDP Foz-Tua: Macrophytes – Ecological Monitoring Program [2011-2015]. 240 records from WildesMoor bei Schwabstedt. 2262 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 206 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 2 records from Description of lithologic section units of IODP Hole 325-M0052A. 25 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 7919 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 212 records from Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 15 records from Bolbelasmus (Bolbelasmus) zagrosensis (Coleoptera: Scarabaeoidea: Bolboceratidae), a new species from Iran, along with an updated key to the western Palaearctic species of the subgenus. 389 records from Hermit crabs of the family Parapaguridae (Crustacea: Decapoda: Anomura) from Australia: species of Strobopagurus Lemaitre, 1989, Sympagurus Smith, 1883 and two new genera.. 251 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 210 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 4 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 11 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 1 records from Notes on the tribe Tongini, with description of a new species of the genus Orthophana from northern Vietnam (Hemiptera: Fulgoroidea: Nogodinidae). 8 records from
Keywords: GBIF; biodiversity; species occurrences